Adhesive laminated film and method for producing adhesive laminated film
By using materials with high thermal stability and low water absorption in the adhesive film diaphragm and performing appropriate surface treatment, the problem of unstable bonding in high-temperature environments is solved, and efficient thermal stability and long-life bonding effect is achieved.
Patent Information
- Application Number
- JP2024159178
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-09-13
- Publication Date
- 2025-03-28
AI Technical Summary
The existing adhesive film diaphragms are prone to gas generation and glue layer peeling problems in high temperature environments, resulting in unstable bonding.
Adhesive film diaphragms with high thermal stability and low water absorption are used, and the adhesive layer contains photocurable resin and acyl bond-containing compound, and the base layer is surface treated to improve the bond strength during the production process.
It realizes the adhesive strength in a high-temperature environment, prevents the glue layer from peeling off, and improves the thermal stability and service life of the diaphragm.
Smart Images

Figure 2025043334000001 
Figure 2025043334000002 
Figure 2025043334000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive laminate film. The present invention also relates to a method for producing an adhesive laminate film. [Background technology]
[0002] Conventionally, adhesive tapes and adhesive films are used to fix components in electronic devices. For example, adhesive tapes and adhesive films are used to adhere a cover panel for protecting the surface of a portable electronic device to a touch panel module or a display panel module, or to adhere a touch panel module to a display panel module. Such adhesive tapes and adhesive films used to fix electronic device components have an adhesive layer containing an adhesive composition, and in addition to high adhesion, functions such as heat resistance, thermal conductivity, and impact resistance are required depending on the environment of the site where they are used (for example, Patent Documents 1 to 3).
[0003] In processing electronic components such as semiconductors, in order to facilitate the handling of the electronic components and prevent them from being damaged, the electronic components are fixed to a support plate via a temporary fixing material made of an adhesive composition, or an adhesive film having an adhesive layer is attached to the electronic components to protect them. For example, when a thick-film wafer cut from a high-purity silicon single crystal or the like is ground to a predetermined thickness to obtain a thin-film wafer, the thick-film wafer is adhered to a support plate via an adhesive composition.
[0004] Adhesive compositions and adhesive films used for electronic components are required to have high adhesion sufficient to firmly fix the electronic components during processing, and also to be able to be peeled off without damaging the electronic components after the processing is completed (hereinafter, also referred to as "high adhesion and easy peeling"). As a means for realizing high adhesion and easy peeling, for example, Patent Document 4 discloses an adhesive sheet using an adhesive in which a polyfunctional monomer or oligomer having a radiation-polymerizable functional group is bonded to the side chain or main chain of the polymer. By utilizing the fact that the polymer has a radiation-polymerizable functional group and is cured by exposure to ultraviolet light, the adhesive strength is reduced by exposure to ultraviolet light during peeling, allowing peeling without leaving any adhesive residue. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-052050 A [Patent Document 2] JP 2015-021067 A [Patent Document 3] JP 2015-120876 A [Patent Document 4] Japanese Patent Application Publication No. 5-32946 Summary of the Invention [Problem to be solved by the invention]
[0006] As electronic components become more powerful, the power applied to them tends to increase, and the electronic components may be exposed to high-temperature environments for longer periods of time. Therefore, adhesive films used to fix electronic components are required to have heat resistance in high-temperature environments. In addition, in order to impart high performance to electronic components, various processes have been performed on electronic components. For example, in a process of forming a metal thin film on the surface of an electronic component by sputtering, a metal thin film with better conductivity can be formed by heating to a high temperature and performing high-temperature processing. In particular, in recent years, high-temperature processing steps have become higher in temperature and longer in duration, and adhesive laminated films with high heat resistance are required. However, when conventional adhesive films are used, voids and outgassing are generated during the high-temperature processing steps, which can cause the adhesive film to peel off.
[0007] On the other hand, when a highly heat-resistant base layer film (e.g., polyimide film) is used to impart heat resistance (thermal decomposition resistance) to the adhesive film, it is possible to suppress the generation of outgassing from the adhesive film in a high-temperature environment, but foaming may occur between the layers of the adhesive film or at the adhesive surface between the adhesive film and the adherend in a high-temperature environment. Therefore, when an electronic component fixed by the adhesive film is exposed to a high-temperature environment, or during a high-temperature processing step using the adhesive film in a high-temperature environment, the adhesive film may peel off from the adherend.
[0008] The present invention aims to provide an adhesive laminated film having excellent heat resistance and capable of suppressing peeling in a high-temperature environment. Another object of the present invention is to provide a method for producing an adhesive laminated film having excellent heat resistance and capable of suppressing peeling in a high-temperature environment. [Means for solving the problem]
[0009] Disclosure 1 relates to an adhesive laminate film having a base layer and at least one adhesive layer on both sides of the base layer, the adhesive laminate film having a 10% weight loss temperature of 425°C or higher and a water absorption rate of 0.60% or lower when allowed to stand for 1 day under conditions of 23°C and 50% RH. The present disclosure 2 is the adhesive laminate film of the present disclosure 1, wherein the adhesive layer contains a curable resin, and the curable resin contains a compound having an imide bond. The present disclosure 3 is the adhesive laminate film according to the present disclosure 1 or 2, wherein the adhesive layer contains a polymerization initiator. The present disclosure 4 is the adhesive laminate film according to the present disclosure 3, in which the polymerization initiator includes a photopolymerization initiator. The present disclosure 5 is the adhesive laminate film according to the present disclosure 1, 2, 3, or 4, wherein the thickness of the adhesive layer is 10 μm or more and 200 μm or less. The present disclosure 6 is an adhesive laminate film according to the present disclosure 1, 2, 3, 4, or 5, wherein the base layer contains a resin (A1) having in its main chain skeleton a repeating unit containing at least one type selected from the group consisting of an ether bond, a ketone group, and an ester bond. The present disclosure 7 is the adhesive laminate film according to the present disclosure 6, wherein the resin (A1) contains at least one resin selected from the group consisting of polyether ether ketone (PEEK), polyethylene naphthalate (PEN), polyimide, and polyamide. The present disclosure 8 is the adhesive laminate film according to the present disclosure 1, 2, 3, 4, 5, 6, or 7, wherein the thickness of the substrate layer is 50 μm or less. A ninth aspect of the present disclosure is the adhesive laminate film of the first, second, third, fourth, fifth, sixth, seventh or eighth aspect of the present disclosure, in which the ratio of the thickness of the base layer to the thickness of the entire adhesive laminate film is 5% or more. The present disclosure 10 is the adhesive laminate film of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, or 9, which has an ultraviolet ray transmittance of 10% or more at a wavelength of 405 nm. An eleventh aspect of the present disclosure is the adhesive laminate film of any one of the first, second, third, fourth, fifth, sixth, seventh, eighth, nineth, and tenth aspects of the present disclosure, wherein the adhesive laminate film has a total thickness of 50 μm or more and 300 μm or less. The present disclosure 12 is an adhesive laminate film according to the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11 used for temporarily fixing electronic components. Disclosure 13 provides a method for producing an adhesive laminate film having a base layer and at least one adhesive layer on both sides of the base layer, the adhesive laminate film having a 10% weight loss temperature of 425°C or higher, the method including a step of drying the base layer. The present invention will be described in detail below.
[0010] The present inventors have investigated the adjustment of the 10% weight loss temperature and water absorption rate of an adhesive laminate film having a base layer and adhesive layers on both sides of the base layer, and have found that it is possible to obtain an adhesive laminate film that is excellent in heat resistance and can suppress peeling in a high-temperature environment, thereby completing the present invention.
[0011] The lower limit of the 10% weight loss temperature of the adhesive laminate film of the present invention is 425° C. When the 10% weight loss temperature of the adhesive laminate film of the present invention is 425° C. or higher, the adhesive laminate film of the present invention has excellent heat resistance. The lower limit of the 10% weight loss temperature of the adhesive laminate film of the present invention is preferably 440° C., and more preferably 450° C. Further, there is no particular preferred upper limit to the 10% weight loss temperature of the adhesive laminate film of the present invention, but the substantial upper limit is about 600°C. At the 10% weight loss temperature of the adhesive laminated film of the present invention described above, the adhesive layer of the adhesive laminated film is an uncured adhesive layer that has not been subjected to a curing operation. The 10% weight loss temperature of the adhesive laminate film of the present invention can be measured by a simultaneous differential thermal-thermogravimetric analyzer. Specifically, it can be measured by the following method. That is, the adhesive laminated film is cut into a size of 5 mm wide x 10 mm long to prepare a test piece. The obtained test piece is weighed in an aluminum pan, and the aluminum pan is set in a differential thermal-thermogravimetric simultaneous measuring device. When the temperature is raised from 30°C to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, the temperature at the point when the mass of the adhesive laminated film is reduced by 10% compared to before the temperature is raised can be obtained as the 10% weight reduction temperature. As the differential thermal-thermogravimetric simultaneous measuring device, for example, STA7200RV (manufactured by Hitachi High-Tech Science Corporation) can be used. Note that the test piece is not laminated with a release PET film to protect the adhesive layer.
[0012] Methods for adjusting the 10% weight loss temperature of the adhesive laminate film of the present invention within the above-mentioned range include, for example, a method of changing the composition of the adhesive layer, a method of changing the type of the base layer, a method of changing the thickness ratio of the adhesive layer to the base layer, and the like.
[0013] The adhesive laminate film of the present invention has an upper limit of water absorption (hereinafter, sometimes simply referred to as "water absorption of the adhesive laminate film") of 0.60% when left to stand for 1 day under conditions of 23°C and 50% RH. When the adhesive laminate film of the present invention has a water absorption of 0.60% or less, foaming occurring between the layers of the film or on the adhesive surface between the film and the adherend in a high-temperature environment can be suppressed, and therefore the adhesive laminate film of the present invention can be prevented from peeling off in a high-temperature environment. The preferred upper limit of the water absorption is 0.50%, and the more preferred upper limit is 0.40%. Although there is no particular preferred lower limit for the water absorption rate, the substantial lower limit is about 0.10%. In the above-mentioned water absorption rate of the adhesive laminated film of the present invention, the adhesive layer of the adhesive laminated film is measured using an uncured adhesive layer that is not subjected to a curing operation. The water absorption rate of the adhesive laminated film can be measured by the following method. That is, the adhesive laminated film was cut into a size of 20 mm wide x 50 mm long to prepare a test piece, and then the test piece was dried for 1 hour in an environment of 130°C and 50% RH. The mass W 0 Furthermore, mass W 0 After the measurement, the test piece is left to stand for one day under conditions of 23°C and 50% RH, and the mass W 1 Measure the obtained W 0 , W 1 The water absorption rate is calculated using the following formula (I). Water absorption rate (%)={(W 1 -W 0 ) / W 0}×100 (I) (W 0 W: Mass of the test piece immediately after drying for 1 hour under 130℃ and 50% RH 1(Weight of test piece after leaving it for 1 day under the conditions of 23℃ and 50% RH)
[0014] Methods for adjusting the water absorption rate of the adhesive laminate film to within the above-mentioned range include, for example, a method of changing the composition of the adhesive layer, a method of changing the type of substrate layer, a method of using a substrate layer that has been dried during the production of the adhesive laminate film described below, and a method of changing the ratio of the thickness of the substrate layer to the total thickness of the film.
[0015] The adhesive laminate film of the present invention has a substrate layer. The substrate layer preferably contains a resin material having excellent heat resistance. Examples of the resin material include a resin (A1) having a repeating unit containing at least one selected from the group consisting of an ether bond, a ketone group, and an ester bond in the main chain skeleton, polyimide, polyamide, etc. Among them, the substrate layer preferably contains the resin (A1). By containing the resin (A1) in the substrate layer, the water absorption rate of the substrate layer becomes smaller, so that the occurrence of foaming during high-temperature processing can be more effectively suppressed, and peeling in a high-temperature environment can be more effectively prevented. Such resin materials may be used alone or in combination of two or more kinds.
[0016] Examples of the resin (A1) include polyether ether ketone (PEEK) and polyethylene naphthalate (PEN).
[0017] At least one surface of the substrate layer preferably has an easy-adhesion layer. By having at least one surface of the substrate layer have an easy-adhesion layer, the adhesion between the adhesive layer and the substrate layer is improved, and the anchoring force of the adhesive layer to the substrate layer at 23° C. is improved. As a result, the handleability of the obtained adhesive laminate film is improved.
[0018] The easy-adhesion layer preferably includes at least one layer selected from a corona-treated layer, a plasma-treated layer, a sandblasted layer, a chemically etched layer, and a treatment-coated layer. The easy-adhesion layer includes at least one layer selected from a corona-treated layer, a plasma-treated layer, a sandblasted layer, a chemically etched layer, and a treatment-coated layer, which improves the adhesion between the adhesive layer and the substrate layer, thereby improving the anchoring force of the adhesive layer to the substrate at 23°C, and improving the handleability of the obtained adhesive laminate film. In particular, it is more preferable that the easy-adhesion layer has a corona-treated layer. The method for forming the corona-treated layer may be, for example, to perform corona treatment on the substrate using a high-frequency power supply (such as "AGI-020" manufactured by Kasuga Electric Co., Ltd.) under conditions of output of 0.3 kW, electrode distance of 1 mm, and speed of 2 m / min to form a corona-treated layer. Alternatively, a commercially available product in which the substrate has been subjected to corona treatment may be used. Examples of the treating agent that forms the treating agent coating layer include polyethyleneimine graft polymers, acrylic polymers, polyimides, bismaleimide resins, silane coupling agents, titanium coupling agents, other known adhesion-imparting agents, and pressure-sensitive adhesives.
[0019] When the easy-adhesion layer is a treatment agent coating layer, the thickness of the treatment agent coating layer is preferably 0.1 μm at the lower limit and 50 μm at the upper limit. When the thickness of the treatment agent coating layer is within the above range, the adhesion between the adhesive layer and the base layer is improved, and the anchoring force of the adhesive layer to the base layer at 23° C. is improved. As a result, the handleability of the obtained adhesive laminate film is improved. The more preferred lower limit of the thickness of the treatment agent coating layer is 1 μm, and the more preferred upper limit is 30 μm. When the easy-adhesion layer is other than the treatment agent coating layer, the thickness of the easy-adhesion layer is not particularly limited, but is substantially 1 nm or more and 50 μm or less.
[0020] The upper limit of the thickness of the substrate layer is preferably 50 μm. By setting the thickness of the substrate layer to 50 μm or less, the substrate layer has a higher ultraviolet transmittance. The upper limit of the thickness of the substrate layer is more preferably 30 μm, and even more preferably 25 μm. The base layer has a preferred lower limit of 5 μm in thickness. When the base layer has a thickness of 5 μm or more, the resulting adhesive laminate film has a firmness and is more excellent in handleability. The base layer has a more preferred lower limit of 10 μm, and a further more preferred lower limit of 12 μm.
[0021] The ratio of the thickness of the base layer to the total thickness of the adhesive laminated film of the present invention is preferably 5% at the lower limit. When the ratio of the thickness of the base layer is 5% or more, the water absorption rate of the obtained adhesive laminated film can be easily adjusted to an appropriate range. The more preferable lower limit of the ratio of the thickness of the base layer is 8%, and the even more preferable lower limit is 10%. The upper limit of the thickness ratio of the substrate layer is preferably 50%. By making the thickness ratio of the substrate layer 50% or less, the adhesive laminated film of the present invention does not become too rigid as a whole, and the adhesive laminated film of the present invention has excellent conformity to the release film for protecting the adhesive layer and the core material used when the adhesive laminated film is rolled. The upper limit of the thickness ratio of the substrate layer is more preferably 40%, and even more preferably 35%.
[0022] The base layer preferably has a lower limit of 50% for the ultraviolet transmittance at a wavelength of 405 nm (hereinafter, sometimes simply referred to as "ultraviolet transmittance"). When the base layer has an ultraviolet transmittance of 50% or more, a sufficient amount of ultraviolet light can be irradiated onto the adhesive layers on both sides, so that the adhesive layers on both sides of the adhesive laminate film can be sufficiently cured. The base layer more preferably has a lower limit of 60%, and even more preferably has a lower limit of 65%. The upper limit of the ultraviolet transmittance of the substrate layer is preferably 70%. By setting the ultraviolet transmittance of the substrate layer to 70% or less, irradiation of the adherend with ultraviolet rays can be suppressed when the adhesive laminated film is irradiated with ultraviolet rays, so that the adhesive laminated film can be cured while suppressing deterioration of the quality of the adherend. The upper limit of the ultraviolet transmittance of the substrate layer is more preferably 68%, and even more preferably 65%. In this specification, the transmittance of ultraviolet light at a wavelength of 405 nm can be measured by using a spectrophotometer (such as "V-670" manufactured by JASCO Corporation).
[0023] The base layer has a glass transition temperature (Tg) of 100° C. or more. When the base layer has a glass transition temperature of 100° C. or more, the heat resistance of the resulting adhesive laminate film is improved. The base layer has a more preferable glass transition temperature of 120° C. or less. Further, the upper limit of the glass transition temperature of the substrate layer is not particularly limited, but the practical upper limit is 300°C. The glass transition temperature of the base layer can be measured, for example, by dynamic viscoelasticity measurement, etc. Specifically, for example, the glass transition temperature can be measured as the temperature at which the loss tangent has a maximum value by performing dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (such as "DVA-200" manufactured by IT Measurement & Control Co., Ltd.) under the measurement conditions of shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz.
[0024] The lower limit of the melting point of the substrate layer is preferably 150° C. When the melting point of the substrate layer is 150° C. or higher, the heat resistance of the obtained adhesive laminate film is further improved. Further, the upper limit of the melting point of the substrate layer is not particularly limited, but the practical upper limit is 400°C. The melting point of the substrate layer can be measured, for example, by the following method. That is, the substrate layer is subjected to differential scanning calorimetry (DSC) using a differential scanning calorimeter (e.g., "DSC-7020" manufactured by Hitachi High-Tech Science Corporation) under the measurement conditions of a nitrogen atmosphere, a heating rate of 10°C / min, and a measurement temperature of 30°C to 500°C, and the melting point of the substrate layer can be measured by reading the temperature showing the endothermic peak from the obtained differential scanning calorimetry curve.
[0025] The adhesive laminate film of the present invention has at least one adhesive layer on both sides of the above-mentioned base layer. The adhesive layer preferably contains a curable resin. The adhesive layer contains a curable resin, so that the adhesive layer has a curable property. Therefore, the adhesive layer can be cured, and the adhesion of the adhesive laminated film during high-temperature processing can be suppressed, and the adhesive laminated film can be easily peeled off at the time of peeling. Examples of the curable resin include photocurable resins and ultraviolet curable resins that are cured by irradiation with light or ultraviolet rays, and thermosetting resins that are cured by heating.
[0026] The curable resin preferably contains a compound having an imide bond. By containing the compound having an imide bond in the curable resin, the adhesive layer has better heat resistance, and the water absorption rate of the adhesive layer can be easily adjusted to an appropriate range, so that the adhesive laminate film obtained can more easily suppress the generation of bubbles in a high-temperature environment. In addition, since the compound having the imide bond has excellent ultraviolet absorption properties, when the curable resin contains a compound having the imide bond, the adhesive layer can be cured more easily by irradiation with ultraviolet light.
[0027] The compound having the imide bond preferably contains a resin having an imide skeleton in the repeating unit of the main chain. The resin having the imide skeleton in the repeating unit of the main chain has excellent heat resistance due to the imide skeleton, and the main chain is unlikely to decompose even in a high-temperature environment of 300°C or more. Therefore, by including a curable resin containing a resin having the imide skeleton in the repeating unit of the main chain, the adhesive laminate film obtained has excellent heat resistance, and the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed. In addition, when the adhesive laminate film is used as a temporary fixing material, it is possible to prevent the adhesion to the adherend from being increased in a high-temperature processing step, and the occurrence of adhesive residue when peeled off from the adherend.
[0028] The resin having an imide skeleton in the repeating unit of the main chain preferably has a constitutional unit represented by the following formula (1).
[0029] [ka]
[0030] In the above formula (1), P 1 is preferably an aromatic group having 5 to 50 carbon atoms. 1 is an aromatic group having 5 to 50 carbon atoms, the adhesive laminate film obtained has better heat resistance. That is, the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed. In addition, when the adhesive laminate film is used as a temporary fixing material, it is possible to further prevent the adhesion to the adherend from being increased in a high-temperature processing step and the occurrence of adhesive residue when peeled off from the adherend.
[0031] In the above formula (1), Q 1 is preferably a substituted or unsubstituted linear, branched or cyclic aliphatic group having 2 to 100 carbon atoms. 1is a substituted or unsubstituted linear, branched or cyclic aliphatic group having from 2 to 100 carbon atoms, the adhesive laminate film obtained has better ultraviolet transmittance. In addition, the adhesive laminate film obtained has better flexibility and can exhibit high conformability to an adherend having irregularities, and when the adhesive laminate film is used as a temporary fixing material, it can be more easily peeled off. Also, the above Q 1 is preferably an aliphatic group derived from a diamine compound. In particular, from the viewpoints of light transparency, flexibility, and compatibility with solvents and other components of the resin having the imide skeleton in the main chain repeating unit, Q is preferably an aliphatic group derived from a diamine compound. 1 is preferably an aliphatic group derived from dimer diamine. The dimer diamine is a diamine compound obtained by reducing and amminating cyclic and acyclic dimer acids obtained as dimers of unsaturated fatty acids, and examples of the dimer diamine include linear, monocyclic, and polycyclic dimer diamines. The dimer diamine may contain a carbon-carbon double bond, or may be a hydrogenated product to which hydrogen has been added.
[0032] The aliphatic group derived from the dimer diamine is preferably at least one group selected from the group consisting of a group represented by the following formula (2-1), a group represented by the following formula (2-2), a group represented by the following formula (2-3), and a group represented by the following formula (2-4). Among these, the group represented by the following formula (2-2) is more preferred.
[0033] [ka]
[0034] In formulas (2-1) to (2-4), R 1 ~R 16 each independently represents a linear or branched hydrocarbon group, and * represents a bond. The bond * is bonded to N in the above formula (1).
[0035] In the above formulas (2-1) to (2-4), R1 ~R 16 The hydrocarbon group represented by may be a saturated hydrocarbon group or an unsaturated hydrocarbon group. 1 and R 2 , R 3 and R 4 , R 5 and R 6 , R 7 and R 8 , R 9 and R 10 , R 11 and R 12 , R 13 and R 14 , and R 15 and R 16 The total number of carbon atoms is preferably 7 or more and 50 or less. When the total number of carbon atoms is within the above range, the obtained adhesive laminate film has better light transmission and flexibility, and also has better compatibility with solvents and other components of the resin having the imide skeleton in the main chain repeating unit. The total number of carbon atoms is more preferably 9 or more, even more preferably 12 or more, and even more preferably 14 or more. The total number of carbon atoms is more preferably 35 or less, even more preferably 25 or less, and even more preferably 18 or less.
[0036] In the group represented by the above formula (2-1), the group represented by the above formula (2-2), the group represented by the above formula (2-3), and the group represented by the above formula (2-4), the optical isomerism is not particularly limited and includes any optical isomerism.
[0037] The resin having an imide skeleton in a repeating unit of its main chain preferably includes a resin having no maleimide group and having an imide skeleton in a repeating unit of its main chain, and more preferably includes a resin having no polymerizable functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of its main chain.
[0038] The resin having no maleimide group and an imide skeleton in the repeating unit of the main chain preferably has a weight average molecular weight of 20,000 or more and 2,000,000 or less. When the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 20,000 or more, the obtained adhesive laminate film has better heat resistance. That is, the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed, and when the adhesive laminate film is used as a temporary fixing material, it is possible to further prevent adhesion to the adherend in a high-temperature processing step and the occurrence of adhesive residue when peeled from the adherend. When the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 2,000,000 or less, the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain has better compatibility with solvents and other components. The weight average molecular weight of the resin that does not have a maleimide group and has an imide skeleton in the repeating unit of the main chain is more preferably 40,000 in lower limit and 600,000 in upper limit, still more preferably 50,000 in lower limit and still more preferably 300,000 in upper limit. In this specification, the weight average molecular weight is measured as a polystyrene equivalent molecular weight by gel permeation chromatography (GPC). Specifically, for example, the measurement can be performed using an APC system (manufactured by Waters) under the conditions of a mobile phase of THF, a flow rate of 1.0 mL / min, a column temperature of 40°C, a sample concentration of 0.2 mass%, and an RI-PDA detector. As the column, HR-MB-M 6.0 x 150 mm (manufactured by Waters) or the like can be used.
[0039] Specific examples of the resin that does not have a maleimide group and has an imide skeleton in the repeating unit of the main chain include resins that have a constitutional unit represented by the above formula (1) and have functional groups at both ends that do not have maleimide groups.
[0040] The resin having a constituent unit represented by the above formula (1) and a functional group not having a maleimide group at both ends may have a constituent unit represented by the following formula (3).
[0041] [ka]
[0042] In formula (3), P 2 represents an aromatic group, and Q 2 represents a group having a substituted or unsubstituted aromatic structure.
[0043] In the above formula (3), P 2 is preferably an aromatic group having 5 to 50 carbon atoms. 2 is an aromatic group having 5 to 50 carbon atoms, the adhesive laminate film obtained has better heat resistance. That is, the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed. In addition, when the adhesive laminate film is used as a temporary fixing material, it is possible to further prevent the adhesion to the adherend from increasing in a high-temperature environment and the occurrence of adhesive residue when peeled off from the adherend.
[0044] In the above formula (3), Q 2 is preferably a substituted or unsubstituted group having an aromatic structure having 5 to 50 carbon atoms. 2 is a substituted or unsubstituted group having an aromatic structure having 5 to 50 carbon atoms, the adhesive laminate film obtained has better heat resistance. That is, the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed. In addition, when the adhesive laminate film is used as a temporary fixing material, it is possible to further prevent the adhesion to the adherend from being increased in a high-temperature processing step and the occurrence of adhesive residue when peeled off from the adherend.
[0045] Examples of the functional group not having a maleimide group include an aliphatic group, an alicyclic group, an aromatic group, an acid anhydride group, an amino group, etc. Specific examples include an unreacted one-terminal constituent group of an acid anhydride or diamine compound that is a raw material for a resin not having a maleimide group and having an imide skeleton in a repeating unit of the main chain. In a resin having a structural unit represented by the above formula (1) and having functional groups at both ends that do not have maleimide groups, the functional groups at both ends that do not have maleimide groups may be the same or different.
[0046] The content of the structural unit represented by the above formula (1) in the resin having a functional group not having a maleimide group at both ends is preferably 30 mol % or more, more preferably 50 mol % or more, and is preferably 90 mol % or less, more preferably 80 mol % or less. When a resin having a structural unit represented by the above formula (1) and having a functional group not having a maleimide group at both ends has a structural unit represented by the above formula (3), the content of the structural unit represented by the above formula (3) is preferably 5 mol % or more, more preferably 10 mol % or more, even more preferably 20 mol % or more, and is preferably 50 mol % or less, more preferably 30 mol % or less. In the constitutional unit represented by the above formula (1) and the constitutional unit represented by the above formula (3), the content ratio of each constitutional unit is within the above range, so that the adhesive laminated film obtained has better heat resistance, and the occurrence of outgassing, voids, and lifting during high-temperature processing can be further suppressed. In addition, when the adhesive laminated film is used as a temporary fixing material, it can be more easily peeled off from the adherend. The structural unit represented by the above formula (1) and the structural unit represented by the above formula (3) may have a block structure consisting of block components in which the respective structural units are arranged consecutively, or may have a random structure in which the respective structural units are arranged randomly.
[0047] Examples of a method for producing the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain include a method of reacting a diamine compound with an aromatic acid anhydride.
[0048] As the diamine compound, either an aliphatic diamine compound or an aromatic diamine compound can be used. By using an aliphatic diamine compound as the diamine compound, the adhesive laminate film obtained has better light transmittance, and has better flexibility, and can exhibit high conformability to an adherend having irregularities, and when the adhesive laminate film is used as a temporary fixing material, it can be more easily peeled off. Furthermore, by using an aromatic diamine compound as the diamine compound, the adhesive laminate film obtained can have superior heat resistance. The diamine compounds may be used alone or in combination of two or more kinds.
[0049] Examples of the aliphatic diamine compound include 1,10-diaminodecane, 1,12-diaminododecane, dimer diamine, 1,2-diamino-2-methylpropane, 1,2-diaminocyclohexane, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,7-diaminoheptane, 1,8-diaminomenthane, 1,8-diaminooctane, 1,9-diaminononane, 3,3'-diamino-N-methyldipropylamine, diaminomaleonitrile, 1,3-diaminopentane, bis(4-amino-3-methylcyclohexyl)methane, 1,2-bis(2-aminoethoxy)ethane, and 3(4),8(9)-bis(aminomethyl)tricyclo(5.2.1.02,6)decane.
[0050] Among the above aliphatic diamine compounds, dimer diamine is preferred from the viewpoints of light transmittance, flexibility, and compatibility with solvents and other components of the resin that does not have the maleimide group and has an imide skeleton in the repeating unit of the main chain.Specific examples of the above dimer diamine include dimer diamines that can constitute at least one group selected from the group consisting of the group represented by the above formula (2-1), the group represented by the formula (2-2), the group represented by the formula (2-3), and the group represented by the formula (2-4).
[0051] Examples of the aromatic diamine compound include 9,10-diaminophenanthrene, 4,4'-diaminooctafluorobiphenyl, 3,7-diamino-2-methoxyfluorene, 4,4'-diaminobenzophenone, 3,4-diaminobenzophenone, 3,4-diaminotoluene, 2,6-diaminoanthraquinone, 2,6-diaminotoluene, 2,3-diaminotoluene, 1,8-diaminonaphthalene, 2,4-diaminotoluene, 2,5-diaminotoluene, 1,4-diaminoanthraquinone, 1,5-diaminotoluene, 1,6-diaminotoluene, 1,8 ... Aminoanthraquinone, 1,5-diaminonaphthalene, 1,2-diaminoanthraquinone, 2,4-cumenediamine, 1,3-bisaminomethylbenzene, 1,3-bisaminomethylcyclohexane, 2-chloro-1,4-diaminobenzene, 1,4-diamino-2,5-dichlorobenzene, 1,4-diamino-2,5-dimethylbenzene, 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, bis(amino-3-chlorophenyl)ethane, bis(4-amino-3,5-dimethylphenyl)methan , bis(4-amino-3,5-diethylphenyl)methane, 9,9'-bis(4-amino-3-ethylphenyl)fluorene, 2,3-diaminonaphthalene, 2,3-diaminophenol, bis(4-amino-5-methylphenyl)methane, bis(4-amino-3-methylphenyl)methane, bis(4-amino-3-ethylphenyl)methane, 4,4'-diaminophenylsulfone, 3,3'-diaminophenylsulfone, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenyl)phenyl)sulfone, 4,4'-Oxydianiline, 4,4'-Diaminodiphenyl Sulfide, 3,4'-Oxydianiline, 2,2-Bis(4-(4-aminophenoxy)phenyl)propane, 1,3-Bis(4-aminophenoxy)benzene, 4,4'-Bis(4-aminophenoxy)biphenyl, 4,4'-Diamino-3,3'-dihydroxybiphenyl, 4,4'-Diamino-3,3'-dimethylbiphenyl, 4,4'-Diamino-3,3'-dimethoxybiphenyl, Bisaniline M, Bisaniline P, 9,9-Bis(4-aminophenyl)fluorene, o-Tolidine Sulfone, 5,5'-Methylenebis(anthranilic acid), 1,Examples of the amines include 3-bis(4-aminophenoxy)-2,2-dimethylpropane, 1,3-bis(4-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)butane, 2,3,5,6-tetramethyl-1,4-phenylenediamine, 3,3',5,5'-tetramethylbenzidine, 4,4'-diaminobenzanilide, 2,2-bis(4-aminophenyl)hexafluoropropane, polyoxyalkylenediamines (e.g., Jeffamine D-230, D400, D-2000, and D-4000 manufactured by Huntsman), 1,3-cyclohexanebis(methylamine), m-xylylenediamine, and p-xylylenediamine.
[0052] Examples of the aromatic acid anhydride include pyromellitic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 1,2,4,5-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-biphenylethertetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, 3,4,9,10-perylenetetracarboxylic acid, 4,4'-sulfonyldiphthalic acid, 1-trifluoromethyl-2,3,5,6-benzenetetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)propane, 2,2-bis(2,3-dicarboxyphenyl)propane, 1,1 ... bis(3,4-dicarboxyphenyl)ethane, 1,1-bis(3,4-dicarboxyphenyl)ethane, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)sulfone, bis(3,4-dicarboxyphenyl)ether, benzene-1,2,3,4-tetracarboxylic acid, 2,3,2',3'-benzophenonetetracarboxylic acid, 2,3,3',4'-benzophenonetetracarboxylic acid, phenanthrene-1,8,9,10-tetracarboxylic acid, pyrazine-2,3,5,6-tetracarboxylic acid, thiophene-2,3,4,5-tetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide, 4,4'-(4,4'-isopropylidenediphenoxy)-bis(phthalic acid) and other carboxylic acid anhydrides.
[0053] The preferred lower limit of the content of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is 10 parts by mass, and the preferred upper limit is 90 parts by mass. When the content of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain is within this range, the obtained adhesive laminated film can be more easily peeled off from the adherend when used as a temporary fixing material. From the viewpoint of further improving the peelability, the more preferred lower limit of the content of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain is 20 parts by mass, and the more preferred upper limit is 80 parts by mass.
[0054] The resin having the imide skeleton in the repeating unit of the main chain preferably contains a resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain. By containing a resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain, the adhesive laminate film obtained is uniformly and quickly polymerized and crosslinked as a whole by irradiation with light, etc., and the elastic modulus increases, so that the adhesive strength is greatly reduced. Therefore, when the adhesive laminate film is used as a temporary fixing material, it is possible to more effectively prevent adhesion from being increased in a high-temperature processing step and the occurrence of adhesive residue when peeled off. When the resin having an imide skeleton in a repeating unit of its main chain includes a resin which does not have the maleimide group and has an imide skeleton in a repeating unit of its main chain, it is preferable that the resin further includes a resin which has a functional group having a carbon-carbon double bond and has an imide skeleton in a repeating unit of its main chain, in addition to the resin which does not have a maleimide group and has an imide skeleton in a repeating unit of its main chain.
[0055] Examples of the functional group having a carbon-carbon double bond include an optionally substituted maleimide group, a citraconimide group, a vinyl ether group, an allyl group, and a (meth)acryloyl group. Among them, an optionally substituted maleimide group is preferred because it provides higher heat resistance. Note that the carbon-carbon double bond contained in an aromatic ring is not considered as the carbon-carbon double bond of the functional group having a carbon-carbon double bond. In this specification, "(meth)acryloyl" means acryloyl or methacryloyl.
[0056] The resin having the functional group having a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain preferably has a functional group equivalent (weight average molecular weight / number of functional groups having a carbon-carbon double bond) of 4000 or less. When the functional group equivalent of the functional group having a carbon-carbon double bond is 4000 or less, the obtained adhesive laminated film has better heat resistance. This is because the resin molecule has a functional group having a carbon-carbon double bond at a density of at least a certain level, which shortens the distance between crosslinks and thus suppresses adhesion enhancement. The functional group equivalent of the functional group having a carbon-carbon double bond is more preferably 3000 or less, and even more preferably 2000 or less. Further, there is no particular preferred lower limit for the functional group equivalent weight of the functional group having a carbon-carbon double bond, but the substantial lower limit is about 600.
[0057] The resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain preferably has a weight average molecular weight of 1000 or more and 100,000 or less. The resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 1000 or more, which makes it easy to form the adhesive layer, and the adhesive laminate film obtained has a certain degree of flexibility, so that it can exhibit high conformability to an adherend having unevenness, and when the adhesive laminate film is used as a temporary fixing material, it can be peeled off more easily. The resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 100,000 or less, which prevents the solubility of the resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain in a solvent from becoming too low. The weight average molecular weight of the resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain is more preferably 1,500 or more and 50,000 or less, and further preferably 2,000 or more and less than 20,000.
[0058] In the resin having a functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of the main chain, the functional group having a carbon-carbon double bond may be present either at a side chain or at a terminal, but is preferably present at both terminals, and more preferably present at the side chain in addition to both terminals. The functional groups having a carbon-carbon double bond at both ends of the resin having the above-mentioned functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain are highly reactive, and can more fully cure the above-mentioned adhesive laminated film by irradiation with light, etc. Therefore, when the adhesive laminated film is used as a temporary fixing material, it is possible to more effectively prevent adhesion from being enhanced in a high-temperature processing step and the occurrence of adhesive residue when peeled off. Furthermore, by having the functional group having the carbon-carbon double bond and the functional group having the carbon-carbon double bond in the side chain of the resin having the imide skeleton in the repeating unit of the main chain, the obtained adhesive laminate film has better heat resistance. This is thought to be because the crosslinking distance is shortened, which further suppresses adhesion enhancement. In addition, by having the functional group having the carbon-carbon double bond and the functional group having the carbon-carbon double bond in the side chain of the resin having the imide skeleton in the repeating unit of the main chain, it becomes easy to adjust the functional group equivalent to 4000 or less while making the weight average molecular weight 1000 or more. This allows the adhesive laminate film to have sufficient initial adhesion, and at the same time, it is possible to more effectively prevent adhesion enhancement and the occurrence of adhesive residue when peeled off.
[0059] As described above, in the resin having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, the functional group having the carbon-carbon double bond may be in either the side chain or the terminal. When either the side chain or the terminal is a functional group other than the functional group having a carbon-carbon double bond (functional group having no carbon-carbon double bond), the functional group having no carbon-carbon double bond may be, for example, an aliphatic group, an alicyclic group, an aromatic group, an acid anhydride group, an amino group, etc. Specifically, the functional group having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain may be an acid anhydride, an unreacted one-end constituent group of a diamine compound, etc., which is a raw material for the resin having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain. When the resin having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain has two or more functional groups having no carbon-carbon double bond in the side chain or the terminal, the functional groups having no carbon-carbon double bond may be the same or different.
[0060] Specific examples of the resin having a functional group having a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain include resins having a constitutional unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of the terminal and the side chain.
[0061] The resin having a structural unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of an end and a side chain may have at least one structural unit selected from the group consisting of a structural unit represented by the following formula (4-1) and a structural unit represented by the following formula (4-2).
[0062] [ka]
[0063] In formula (4-1), P 3 represents an aromatic group, and Q 3 represents a group having a substituted or unsubstituted aromatic structure, and in formula (4-2), P 4 represents an aromatic group, R represents a substituted or unsubstituted branched aliphatic group or aromatic group, and X represents a functional group having a carbon-carbon double bond.
[0064] P in the above formula (4-1) 3 and P in the above formula (4-2) 4 is preferably an aromatic group having 5 to 50 carbon atoms. 3 and P 4 is an aromatic group having 5 to 50 carbon atoms, the adhesive laminate film obtained has better heat resistance. That is, the occurrence of outgassing, voids, and lifting during high-temperature processing can be further suppressed. In addition, when the adhesive laminate film is used as a temporary fixing material, it is possible to further prevent the adhesion to the adherend from increasing in a high-temperature environment and the occurrence of adhesive residue when peeled off from the adherend.
[0065] In the above formula (4-1), Q 3 is preferably a substituted or unsubstituted group having an aromatic structure having 5 to 50 carbon atoms. 3is a substituted or unsubstituted group having an aromatic structure having 5 to 50 carbon atoms, the adhesive laminate film obtained has better heat resistance. That is, the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed. In addition, when the adhesive laminate film is used as a temporary fixing material, it is possible to further prevent the adhesion to the adherend from being increased and the occurrence of adhesive residue when peeled off from the adherend.
[0066] In the above formula (4-2), R is preferably a substituted or unsubstituted branched aliphatic or aromatic group having 2 to 100 carbon atoms. When R is a substituted or unsubstituted branched aliphatic or aromatic group having 2 to 100 carbon atoms, the obtained adhesive laminate film has excellent flexibility and can exhibit high conformability to an adherend having irregularities, and when the adhesive laminate film is used as a temporary fixing material, it can be peeled off more easily.
[0067] In the above formula (4-2), R is an aromatic group having an aromatic ester group or an aromatic ether group, and the aromatic ester group or the aromatic ether group in R is preferably bonded to X. Here, the term "aromatic ester group" means a group in which an ester group is directly bonded to an aromatic ring, and the term "aromatic ether group" means a group in which an ether group is directly bonded to an aromatic ring. By making the moiety bonded to the ester group or ether group an aromatic group in this way, the obtained adhesive laminate film has better heat resistance. That is, the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed, and when the adhesive laminate film is used as a temporary fixing material, it is possible to further prevent adhesion enhancement to the adherend in a high-temperature processing step and the occurrence of adhesive residue when peeled off from the adherend. On the other hand, by bonding X to R via an aromatic ester group or an aromatic ether group, the carbon-carbon double bond in X is not conjugated with R, and therefore does not hinder polymerization and crosslinking when heated or irradiated with light.
[0068] The content of the structural unit represented by the above formula (1) in the resin having a functional group having a carbon-carbon double bond at least in one of an end or a side chain is preferably 30 mol % or more, more preferably 50 mol % or more, and is preferably 90 mol % or less, more preferably 80 mol % or less. When a resin having a structural unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of an end and a side chain has a structural unit represented by the above formula (4-1), the content of the structural unit represented by the above formula (4-1) is preferably 5 mol % or more, more preferably 10 mol % or more, even more preferably 20 mol % or more, and is preferably 50 mol % or less, more preferably 30 mol % or less. When a resin having a structural unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of an end and a side chain has a structural unit represented by the above formula (4-2), the content of the structural unit represented by the above formula (4-2) is preferably 10 mol % or more, more preferably 20 mol % or more, and preferably 50 mol % or less, more preferably 30 mol % or less. In the constitutional unit represented by the above formula (1), the constitutional unit represented by the above formula (4-1), and the constitutional unit represented by the above formula (4-2), the content ratio of each constitutional unit is within the above range, so that the obtained adhesive laminated film has better heat resistance. That is, the occurrence of outgassing, voids, and lifting in a high-temperature environment can be further suppressed. In addition, when the adhesive laminated film is used as a temporary fixing material, it can be more easily peeled off from the adherend. The structural unit represented by the above formula (1), the structural unit represented by the above formula (4-1), and the structural unit represented by the above formula (4-2) may have a block structure consisting of block components in which the respective structural units are arranged consecutively, or may have a random structure in which the respective structural units are arranged randomly.
[0069] Examples of a method for producing a resin having a functional group with a carbon-carbon double bond and an imide skeleton in a repeating unit of the main chain include the following methods. That is, first, a diamine compound is reacted with an aromatic acid anhydride to prepare an imide compound. Then, a compound having a functional group reactive with the functional group and a functional group having a carbon-carbon double bond (hereinafter, also referred to as a "functional group-containing unsaturated compound") is reacted with the functional group of the imide compound to obtain a resin having the functional group having the carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain. Alternatively, a resin having a functional group having a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain can be obtained by reacting a diamine compound with an aromatic acid anhydride to prepare an imide compound and then reacting the terminal of the imide compound with, for example, maleic anhydride.
[0070] As the diamine compound and aromatic acid anhydride used in the method for producing a resin having a functional group with a carbon-carbon double bond and having an imide skeleton in a repeating unit of the main chain, the same compounds as those used in the method for producing a resin having no maleimide group and having an imide skeleton in a repeating unit of the main chain can be used.
[0071] The functional group-containing unsaturated compound is selected according to the functional group at the end or side chain of the imide compound. For example, when the functional group at the end or side chain of the imide compound is a hydroxyl group, examples of the functional group-containing unsaturated compound include a maleimide compound having a carboxy group, a vinyl compound having an ether group, an allyl compound having a glycidyl group, an allyl ether compound having a glycidyl group, a vinyl ether compound having a glycidyl group, an allyl compound having an isocyanate group, and a (meth)acryloyl compound having an isocyanate group. Furthermore, for example, when the functional group at the end or side chain of the imide compound is a carboxy group, examples of the functional group-containing unsaturated compound include an allyl compound having a hydroxyl group, an allyl compound having a glycidyl group, an allyl ether compound having a glycidyl group, and a vinyl ether compound having a glycidyl group. Examples of the maleimide compound having a carboxy group include maleimide acetate, maleimidopropionic acid, maleimidobutyric acid, maleimidohexanoic acid, trans-4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid, and 19-maleimido-17-oxo-4,7,10,13-tetraoxa-16-azanonadecanoic acid. An example of the vinyl compound having an ether group is butyl vinyl ether. An example of the allyl compound having a glycidyl group is diallyl monoglycidyl isocyanurate. Examples of the allyl ether compound having a glycidyl group include allyl glycidyl ether, glycerin diallyl monoglycidyl ether, and the like. Examples of the vinyl ether compound having a glycidyl group include glycidyloxyethyl vinyl ether, glycidyloxybutyl vinyl ether, glycidyloxyhexyl vinyl ether, glycidyl diethylene glycol vinyl ether, and glycidyl cyclohexane dimethanol monovinyl ether. The allyl compound having an isocyanate group includes, for example, allyl isocyanate. Examples of the (meth)acryloyl compound having an isocyanate group include 2-(meth)acryloyloxyethyl isocyanate. Examples of the allyl compound having a hydroxyl group include trimethylolpropane diallyl ether and pentaerythritol triallyl ether.
[0072] The content of the resin having the functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is preferably 10 parts by mass, and preferably 100 parts by mass. When the content of the resin having the functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is within this range, the adhesive laminated film can be peeled off more easily at the time of peeling. From the viewpoint of further improving the peelability, the content of the resin having the functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is more preferably 20 parts by mass, even more preferably 30 parts by mass, more preferably 90 parts by mass, even more preferably 80 parts by mass, and even more preferably 70 parts by mass.
[0073] When the compound having an imide bond does not have the maleimide group and contains a resin having an imide skeleton in a repeating unit of the main chain, it is preferable that the compound having an imide bond further contains a polyfunctional monomer or polyfunctional oligomer (hereinafter simply referred to as "polyfunctional monomer or polyfunctional oligomer") having two or more functional groups having a carbon-carbon double bond in the molecule and having a molecular weight of 5,000 or less. In addition, when the compound having an imide bond has the functional group having a carbon-carbon double bond and contains a resin having an imide skeleton in a repeating unit of the main chain, the compound having an imide bond may further contain the polyfunctional monomer or polyfunctional oligomer. By including the polyfunctional monomer or polyfunctional oligomer, the adhesive laminate film can be more efficiently three-dimensionally reticulated by irradiation with light, etc. In particular, when the adhesive laminate film is used as a temporary fixing material, it is possible to more effectively prevent adhesion from increasing at high temperatures and to more effectively prevent adhesive residue from being left behind when peeled off.
[0074] In addition, when the resin having the imide skeleton in the repeating unit of the main chain is not reactive, the curable resin needs to have reactivity as a whole by further containing another component having a reactive functional group. As such another component having a reactive functional group, it is preferable to use the polyfunctional monomer or polyfunctional oligomer. As an example of a case where the resin having the imide skeleton in the repeating unit of the main chain is not reactive, for example, the resin having the imide skeleton in the repeating unit of the main chain does not have the maleimide group and only contains a resin having the imide skeleton in the repeating unit of the main chain.
[0075] Examples of the functional group having a carbon-carbon double bond in the polyfunctional monomer or oligomer include an optionally substituted maleimide group, a citraconimide group, a vinyl ether group, an allyl group, and a (meth)acryloyl group. Among them, an optionally substituted maleimide group is preferred because it provides higher heat resistance. In particular, the polyfunctional monomer or oligomer is preferably a bismaleimide compound.
[0076] The polyfunctional monomer or oligomer preferably has a group derived from a diamine compound. As the diamine compound, either an aliphatic diamine compound or an aromatic diamine compound can be used, but an aliphatic diamine compound is preferred. That is, the polyfunctional monomer or oligomer more preferably has an aliphatic group derived from a diamine compound. By using an aliphatic diamine compound as the diamine compound, the adhesive laminate film obtained has better light transmittance. In addition, the adhesive laminate film obtained has better flexibility, can exhibit high conformability to an adherend having unevenness, and can be more easily peeled off when used as a temporary fixing material.
[0077] Among the above aliphatic diamine compounds, the above dimer diamines are preferred from the viewpoints of light transmittance, flexibility, and compatibility with the solvent of the polyfunctional monomer or polyfunctional oligomer and other components.
[0078] The content of the polyfunctional monomer or polyfunctional oligomer in 100 parts by mass of the curable resin is preferably 5 parts by mass at the lower limit and 90 parts by mass at the upper limit. When the content of the polyfunctional monomer or polyfunctional oligomer is within this range, the adhesive laminated film can be peeled more easily at the time of peeling. From the viewpoint of further improving the peelability, the content of the polyfunctional monomer or polyfunctional oligomer is more preferably 10 parts by mass at the lower limit and 50 parts by mass at the upper limit.
[0079] When the compound having an imide bond contains a resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain, and the polyfunctional monomer or oligomer, the preferred lower limit of the total content of the resin having a functional group with a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, and the polyfunctional monomer or oligomer in 100 parts by mass of the curable resin is 20 parts by mass, and the preferred upper limit is 80 parts by mass. When the total content of the resin having a functional group with a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, and the polyfunctional monomer or oligomer is within this range, the adhesive laminate film can be more easily peeled off at the time of peeling. From the viewpoint of further improving the releasability, the lower limit of the total content of the resin having a functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of its main chain, and the polyfunctional monomer or polyfunctional oligomer is more preferably 30 parts by mass, even more preferably 40 parts by mass, still more preferably 50 parts by mass, and more preferably 70 parts by mass.
[0080] The compound having an imide bond preferably contains a compound having a maleimide group. By containing the compound having a maleimide group, the adhesive laminate film obtained has better heat resistance. The compound having a maleimide group is preferably a bismaleimide compound, or a resin having a maleimide group and an imide skeleton in a repeating unit of the main chain. That is, the compound having an imide bond preferably includes the bismaleimide compound as the polyfunctional monomer or polyfunctional oligomer, or the compound having an imide bond preferably includes a functional group having a carbon-carbon double bond, and the resin having an imide skeleton in a repeating unit of the main chain preferably includes a resin having a maleimide group as the functional group having a carbon-carbon double bond.
[0081] The adhesive layer preferably further contains a polymerization initiator. The polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator, but is preferably a photopolymerization initiator from the viewpoint of storage stability.
[0082] Examples of the photopolymerization initiator include those that are activated by irradiation with light having a wavelength of 250 to 800 nm. In particular, the photopolymerization initiator has a molar absorption coefficient at 405 nm of preferably 10 ml / (g·cm) or more, since the photopolymerization initiator is unlikely to overlap with the absorption wavelength of the curable resin and is sufficiently activated when the adhesive laminated film is irradiated with light. The molar absorption coefficient at 405 nm of the photopolymerization initiator is more preferably 200 ml / (g·cm), and even more preferably 405 ml / (g·cm). The molar absorption coefficient at 405 nm has no particular upper limit, but is preferably 1.0×10 6 The practical upper limit is about ml / (g cm).
[0083] Examples of the photopolymerization initiator include acetophenone derivatives, benzoin ether compounds, ketal derivatives, phosphine oxide derivatives, and oxime ester compounds. The acetophenone derivatives include, for example, methoxyacetophenone. Examples of the benzoin ether compounds include benzoin propyl ether and benzoin isobutyl ether. Examples of the ketal derivative include benzyl dimethyl ketal and acetophenone diethyl ketal. Examples of the phosphine oxide derivatives include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the like. Examples of the oxime ester compound include 1-(O-acetyloxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime)-1,2-octadione, and the like. Further, examples of the photopolymerization initiator include bis(η5-cyclopentadienyl)titanocene derivative compounds, benzophenone, Michler's ketone, chlorothioxanthone, dodecylthioxanthone, dimethylthioxanthone, diethylthioxanthone, α-hydroxycyclohexylphenyl ketone, and 2-hydroxymethylphenylpropane. These photopolymerization initiators may be used alone or in combination of two or more kinds.
[0084] The content of the polymerization initiator is preferably 0.1 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. When the content of the polymerization initiator is within this range, the adhesive laminated film is uniformly and quickly polymerized and crosslinked as a whole by irradiation with light or the like, and the elastic modulus increases, so that the adhesive strength is greatly reduced. In particular, when the adhesive laminated film is used as a temporary fixing material, it is possible to prevent adhesion from being enhanced in a high-temperature environment and the occurrence of adhesive residue when peeled off. The more preferable lower limit of the content of the polymerization initiator is 0.3 parts by mass, and the more preferable upper limit is 3 parts by mass.
[0085] The adhesive layer preferably further contains an inorganic filler. By containing the above-mentioned inorganic filler, the adhesive laminate film obtained can suppress a decrease in elastic modulus at high temperatures, and peeling of the adhesive laminate film can be further suppressed even in high-temperature environments of 300°C or higher.
[0086] Examples of the inorganic filler include at least one inorganic filler selected from the group consisting of oxides of silicon, titanium, aluminum, calcium, boron, magnesium, and zirconia, and composites thereof. Among these, silica and talc are preferred because they are commercially available at low cost and easily available.
[0087] The inorganic filler may be surface-modified. Examples of the functional group that may be used to modify the surface of the inorganic filler include an alkylsilane group, a methacryloyl group, and a dimethylsiloxane group. Among these, the dimethylsiloxane group is preferred because it has a suitable hydrophobicity.
[0088] The preferred lower limit of the average particle size of the inorganic filler is 5 nm, and the preferred upper limit is 30 μm. By having the average particle size of the inorganic filler within this range, the adhesive laminated film obtained can be more suppressed from peeling off in a high temperature environment, and when the adhesive laminated film is used as a temporary fixing material, it can be peeled off by peeling treatment. The more preferred lower limit of the average particle size of the inorganic filler is 10 nm, and the more preferred upper limit is 20 μm, and the even more preferred lower limit is 15 nm, and the even more preferred upper limit is 15 μm. The average particle size can be determined, for example, by observing 50 particles of any inorganic filler using an electron microscope or an optical microscope and calculating the average particle size of each inorganic filler, or by performing laser diffraction particle size distribution measurement.
[0089] The content of the inorganic filler is preferably 1 part by mass at the lower limit and 20 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the inorganic filler being within this range, the adhesive laminated film obtained can be more suppressed from peeling off in a high temperature environment, and when the adhesive laminated film is used as a temporary fixing material, it can be peeled off by peeling treatment at the time of peeling. The more preferred lower limit of the content of the inorganic filler is 3 parts by mass, the more preferred upper limit is 15 parts by mass, the even more preferred lower limit is 5 parts by mass, and the even more preferred upper limit is 10 parts by mass.
[0090] When the adhesive laminate film of the present invention is used as a temporary fixing material, the adhesive layer preferably further contains a surface conditioner. By containing the surface conditioner in the adhesive layer, the surface conditioner bleeds out to the adherend interface, and the removability of the obtained adhesive laminate film is further improved. Examples of the surface conditioner include silicone-based surface conditioners, fluorine-based surface conditioners, acrylic surface conditioners, etc. These surface conditioners have excellent heat resistance, and therefore, by containing the surface conditioner in the adhesive layer, the adhesive layer is prevented from burning even after high-temperature processing at 300° C. or more, and the surface conditioner bleeds out to the adherend interface during peeling, making peeling easier. Among these, silicone-based surface conditioners are preferred from the viewpoint of environmental friendliness and ease of disposal, while acrylic-based surface conditioners are preferred from the viewpoint of preventing contamination of the adherend by silicone.
[0091] The surface conditioner preferably has a functional group capable of crosslinking with the curable resin. Since the surface conditioner has a functional group capable of crosslinking with the curable resin, the surface conditioner reacts chemically with the curable resin by irradiation with light or by reaction with a crosslinking agent, etc., and is incorporated into the curable resin. This makes it possible to prevent the surface conditioner from adhering to the adherend and contaminating it. Examples of the functional group capable of crosslinking with the curable resin include a carboxy group, a radically polymerizable unsaturated bond (e.g., a vinyl group, a (meth)acryloyl group, or a maleimide group which may be substituted), a hydroxy group, an amide group, an isocyanate group, and an epoxy group.
[0092] Examples of the acrylic surface conditioner include acrylic copolymers, and specific examples thereof include BYK-394, BYK-350, BYK-381 (all manufactured by BYK-Chemie), Disparlon 1970 (manufactured by Kusumoto Chemical Industries, Ltd.), and the like.
[0093] Examples of the silicone compound having a functional group capable of crosslinking with the curable resin include silicone oil, silicone diacrylate, silicone graft copolymer, etc. Specifically, a silicone compound having a siloxane skeleton in the main chain and a functional group having a carbon-carbon double bond in the side chain or at the end is preferred. The silicone compound having a siloxane skeleton in the main chain and a functional group having a carbon-carbon double bond in the side chain or at the terminal is preferred. The silicone compound having a siloxane skeleton in the main chain and a functional group having a carbon-carbon double bond in the side chain or at the end is preferably at least one selected from the group consisting of a silicone compound represented by the following formula (5-1), a silicone compound represented by the following formula (5-2), and a silicone compound represented by the following formula (5-3): These silicone compounds are particularly excellent in heat resistance and have high polarity, so that they easily bleed out from the adhesive laminate film.
[0094] [ka]
[0095] X in the above formulae (5-1) to (5-3) and Y in the above formulae (5-1) and (5-3) each independently represent an integer of 0 or more and 1200 or less, and R in the above formulae (5-1) to (5-3) represents a functional group having a carbon-carbon double bond.
[0096] In the above formulas (5-1) to (5-3), examples of the functional group having a carbon-carbon double bond represented by R include an optionally substituted maleimide group, a citraconimide group, a vinyl ether group, an allyl group, and a (meth)acryloyl group. Among these, an optionally substituted maleimide group is preferred because the adhesive laminate film obtained has better heat resistance. In addition, when there are multiple Rs in the above formulas (5-1) to (5-3), each R may be the same or different.
[0097] Among the silicone compounds represented by the above formulas (5-1) to (5-3), commercially available examples include EBECRYL350, EBECRYL1360 (both manufactured by Daicel-Allnex Corporation), etc. Other examples include BYK-UV3500 (manufactured by BYK-Chemie Corporation), TEGO RAD2250 (manufactured by Evonik Corporation) (in both cases, R is an acryloyl group), etc.
[0098] Examples of the fluorine-based surface conditioner include hydrocarbon compounds having fluorine atoms.
[0099] The content of the surface conditioner is preferably 0.1 parts by mass at the lower limit and 20 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the surface conditioner being within this range, the adhesive laminated film obtained does not contaminate the adherend and has excellent peelability. From the viewpoint of further improving peelability while suppressing contamination, the more preferred lower limit of the content of the surface conditioner is 0.3 parts by mass and the more preferred upper limit is 10 parts by mass. In addition, since the adhesive laminate film of the present invention has excellent heat resistance, it can exert a sufficient effect even if the content of the surface conditioner is relatively small, and therefore, the possibility of contamination by the silicone compound or fluorine compound can be further reduced.
[0100] When the adhesive laminated film of the present invention is used as a temporary fixing material, it may further contain a gas generating agent. By containing the gas generating agent, even after high-temperature processing at 300°C or more, the gas generated by light irradiation or the like is released at the interface with the adherend, so that the adherend can be peeled off more easily and without leaving any adhesive residue. In addition, even when a thin adherend is peeled off after high-temperature processing at 300°C or more, damage to the adherend can be prevented.
[0101] The gas generating agent preferably has a weight loss rate of 5% or less at 300°C when heated from 30°C to 300°C at a heating rate of 10°C / min in a nitrogen atmosphere in TG-DTA (thermogravimetry-differential thermal analysis) measurement. If the weight loss rate is 5% or less, the gas generating agent is less likely to decompose even when a high-temperature processing treatment is performed at 300°C or higher, and the adhesive laminated film has better heat resistance. In other words, peeling can be further suppressed during high-temperature processing, and increased adhesion in a high-temperature environment and the occurrence of adhesive residue during peeling can be further prevented. The above TG-DTA (thermogravimetry-differential thermal analysis) measurement can be carried out using, for example, a TG-DTA device (manufactured by Hitachi High-Tech Science Corporation, "STA7200RV") or the like.
[0102] The gas generating agent may be, for example, a gas generating agent that generates gas by heating, a gas generating agent that generates gas by irradiating light, etc. Among them, a gas generating agent that generates gas by irradiating light is preferred, and a gas generating agent that generates gas by irradiating ultraviolet light is more preferred. These gas generating agents may be used alone or in combination of two or more kinds. Examples of the gas generating agent include tetrazole compounds or their salts, triazole compounds or their salts, azo compounds, azide compounds, xanthone acetate, carbonates, etc. These gas generating agents may be used alone or in combination of two or more. Among them, tetrazole compounds or their salts are preferred because of their excellent heat resistance.
[0103] The content of the gas generating agent is preferably 5 parts by mass at the lower limit and 50 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. By the content of the gas generating agent being within this range, the adhesive laminated film obtained has particularly excellent peelability. The more preferred lower limit of the content of the gas generating agent is 8 parts by mass, and the more preferred upper limit is 30 parts by mass.
[0104] The adhesive layer may contain known additives, such as a photosensitizer, a heat stabilizer, an antioxidant, an antistatic agent, a plasticizer, a surfactant, and a wax.
[0105] The adhesive layer has a water absorption rate of preferably 1.0% or less when left to stand for 1 day under conditions of 23°C and 50% RH. When the water absorption rate of the adhesive layer is 1.0% or less, the water absorption rate of the adhesive laminate film obtained can be more easily adjusted to within the above range. The water absorption rate of the adhesive layer is more preferably 0.9% or less, and even more preferably 0.8% or less. Further, although there is no particular preferred lower limit for the water absorption rate of the adhesive layer, the substantial lower limit is about 0.2%. The adhesive layer at the water absorption rate mentioned above is an uncured adhesive layer. The water absorption rate of the adhesive layer can be measured by the same method as that for the water absorption rate of the adhesive laminate film of the present invention described above.
[0106] The adhesive layer preferably has an anchor strength of 0.03 N / 25 mm at 23° C. to the substrate layer when uncured. When the adhesive layer has an anchor strength of 0.03 N / 25 mm or more at 23° C. to the substrate layer, peeling at the interface between the adhesive layer and the substrate layer can be suppressed, and the handleability of the resulting adhesive laminate film is improved. The more preferable lower limit of the anchor strength of the adhesive layer to the substrate layer at 23° C. is 0.05 N / 25 mm. Further, there is no particular preferred upper limit to the anchoring strength of the adhesive layer to the base layer at 23° C., but a practical upper limit is about 20 N / 25 mm. The anchoring strength of the adhesive layer to the base layer at 23° C. is measured by the following method. That is, one side of a commercially available double-sided tape (Sekisui Chemical Co., Ltd., "3810H" etc.) is attached to a SUS plate that has been washed with ethanol and then wiped dry, and then the adhesive layer of the adhesive laminated film of the present invention that is not to be measured is overlapped with the other side of the double-sided tape, so that the adhesive layer of the adhesive laminated film of the present invention to be measured faces up. Furthermore, a 25 mm wide silicone tape (Sliontec Co., Ltd., "6260-01" etc.) is pressed against the exposed adhesive layer of the adhesive laminated film of the present invention by moving a 2 kg hand roller back and forth once at a speed of 300 mm / min. A 25 mm wide cut is made along the silicone tape in the adhesive layer pressed against the silicone tape, and the test sample is prepared by curing at 23°C and 50% RH for 1 hour. The obtained test sample is subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "AG-IS" or the like) in accordance with JIS Z0237, and the adhesive layer pressed onto the silicon tape is peeled off from the base layer to measure the 90° peel strength of the adhesive layer against the base layer. The obtained 180° peel strength is regarded as the anchor strength of the adhesive layer against the base layer at 23°C.
[0107] When the adhesive laminate film of the present invention is a one-sided adhesive laminate film, the anchor strength of the adhesive layer to the substrate layer at 23° C. is measured by the following method. That is, one side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") is attached to a SUS plate that has been washed with ethanol and then wiped dry, and then the other side of the double-sided tape is placed over the adhesive layer of the adhesive laminated film of the present invention to be measured. Furthermore, a 25 mm wide silicone tape (manufactured by Sliontec Co., Ltd., "6260-01") is pressed onto the adhesive layer of the adhesive laminated film of the present invention by moving a 2 kg hand roller back and forth once at a speed of 300 mm / min. A 25 mm wide cut is made along the silicone tape in the adhesive layer pressed onto the silicone tape, and the adhesive layer is aged at 23°C and 50% RH for 1 hour to prepare a test sample. The obtained test sample is subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "AG-IS" or the like) in accordance with JIS Z0237, and the adhesive layer pressed onto the silicon tape is peeled off from the base layer to measure the 90° peel strength of the adhesive layer against the base layer. The obtained 90° peel strength is regarded as the anchor strength of the adhesive layer against the base layer at 23°C.
[0108] The adhesive layer is formed by irradiating the adhesive laminate film with light of 405 nm wavelength from an ultra-high pressure mercury lamp with an integrated light intensity of 20,000 mJ / cm 2 The anchoring force of the adhesive layer to the substrate layer at 23°C after irradiation with light having a wavelength of 405 nm is preferably 0.10 N / 25 mm. When the adhesive layer has an anchoring force of 0.10 N / 25 mm or more at 23°C after irradiation with light having a wavelength of 405 nm, peeling at the interface between the adhesive layer and the substrate layer can be suppressed, and the handleability of the resulting adhesive laminate film is improved. The more preferable lower limit of the anchoring force of the adhesive layer to the substrate layer at 23°C after irradiation with light having a wavelength of 405 nm is 0.15 N / 25 mm. Further, there is no particular preferred upper limit to the anchoring force of the adhesive layer to the base layer at 23° C. after irradiation with light having a wavelength of 405 nm, but a practical upper limit is about 20 N / 25 mm. The anchor strength of the adhesive layer to the base layer at 23°C after irradiation with light of 405 nm wavelength was measured by a method using an ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The measurement can be performed by using the adhesive laminate film irradiated for 300 seconds so that the adhesive laminate film is irradiated with light having a wavelength of 405 nm from an ultra-high pressure mercury lamp, either from the base layer side or from the adhesive layer side. When the adhesive laminate film is irradiated with light from the adhesive layer side, the light is irradiated without removing the separator that protects the adhesive layer.
[0109] Methods for adjusting the anchoring strength of the adhesive layer to the substrate layer at 23°C and the anchoring strength of the adhesive layer to the substrate layer at 23°C after irradiation with light having a wavelength of 405 nm include, for example, a method of directly applying an adhesive to the substrate layer when producing an adhesive laminate film, a method of subjecting the substrate layer to surface treatment such as corona treatment, plasma treatment, sandblasting, chemical etching, or application of a treatment agent when producing an adhesive laminate film, a method of lowering the glass transition temperature (Tg) of the adhesive layer, and adjusting the type and content of a surface conditioner contained in the adhesive layer.
[0110] The adhesive layer has a preferred lower limit of a shear storage modulus of 1.0×10 at 23° C. in an uncured state. 4 The shear storage modulus of the adhesive layer at 23°C is 1.0 x 10 4 The more preferable lower limit of the shear storage modulus at 23° C. of the adhesive layer is 5.0×10 Pa or more, the obtained adhesive laminate film has better heat resistance. 4 Pa, and a more preferable lower limit is 1.0×10 5 It is Pa. The preferred upper limit of the shear storage modulus of the adhesive layer at 23° C. is 5.0×10 7 The shear storage modulus of the adhesive layer at 23°C is 5.0 × 10 7 By setting the shear storage modulus at 23° C. to 0.5 Pa or less, the anchoring force of the adhesive layer to the base layer at 23° C. is further improved. A more preferable upper limit of the shear storage modulus at 23° C. of the adhesive layer is 3.0×10 7 Pa, and more preferably the upper limit is 1.0×10 7 It is Pa. The shear storage modulus of the adhesive layer at 23° C. can be measured, for example, by dynamic viscoelasticity measurement, etc. Specifically, the adhesive layer is laminated to a thickness of about 1 mm to prepare a measurement sample consisting of only the adhesive layer, and the dynamic viscoelasticity measurement is performed using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200", etc.) under the conditions of shear mode, heating rate of 10° C. / min, measurement temperature of 0° C. to 300° C., and frequency of 10 Hz.
[0111] The adhesive layer was exposed to light of 405 nm wavelength from an ultra-high pressure mercury lamp with an integrated light intensity of 20,000 mJ / cm 2 The preferred lower limit of the tensile storage modulus at 23° C. after irradiation so as to satisfy the following conditions (hereinafter, simply referred to as the “tensile storage modulus at 23° C. after irradiation of the adhesive layer with light having a wavelength of 405 nm”) is 1.0×10 8 The tensile storage modulus of the adhesive layer at 23° C. after irradiation with light having a wavelength of 405 nm is 1.0×10 8 The more preferable lower limit of the tensile storage modulus at 23° C. after irradiation of the adhesive layer with light having a wavelength of 405 nm is 1.5×10 8 N / 25mm, and a more preferable lower limit is 2.0×10 8 N / 25mm. In addition, the preferred upper limit of the tensile storage modulus at 23° C. after irradiation of the adhesive layer with light having a wavelength of 405 nm is 5.0×10 9The tensile storage modulus of the adhesive layer at 23° C. after irradiation with light having a wavelength of 405 nm is 5.0×10 9 A more preferable upper limit of the tensile storage modulus at 23° C. after irradiation of the adhesive layer with light having a wavelength of 405 nm is 4.0×10 Pa or less. 9 N / 25mm, and more preferably an upper limit of 3.0×10 9 N / 25mm. The tensile storage modulus at 23°C after irradiation of the adhesive layer with light having a wavelength of 405 nm was measured by irradiating a measurement sample obtained by the above-mentioned method for measuring the shear storage modulus at 23°C of the adhesive layer with light having a wavelength of 405 nm using an ultra-high pressure mercury lamp with an integrated light intensity of 20,000 mJ / cm 2 The shear storage modulus of the adhesive layer at 23°C can be measured in the same manner as above, except that the dynamic viscoelasticity measurement is performed in tensile mode, using a measurement sample that has been irradiated so as to satisfy the above condition.
[0112] Methods for adjusting the tensile storage modulus of the adhesive layer at 23°C and the tensile storage modulus of the adhesive layer at 23°C after irradiation with light having a wavelength of 405 nm include, for example, changing the composition of the adhesive layer (e.g., adding an inorganic filler), adjusting the glass transition temperature (Tg) of the adhesive layer, and adjusting the degree of crosslinking of the curable resin.
[0113] The adhesive layer preferably has a glass transition temperature (Tg) in an uncured state of greater than 0°C and less than 100°C. When the adhesive layer has a glass transition temperature of greater than 0°C, the heat resistance of the resulting adhesive laminate film is further improved. When the adhesive layer has a glass transition temperature of less than 100°C, the anchoring force of the adhesive layer to the base layer is further improved. The adhesive layer's glass transition temperature is more preferably 5°C in lower limit, 95°C in upper limit, 8°C in even more preferred lower limit, and 90°C in even more preferred upper limit. The glass transition temperature of the adhesive layer can be measured, for example, by dynamic viscoelasticity measurement, etc. Specifically, a measurement sample consisting of only the adhesive layer is prepared by laminating the adhesive layer to a thickness of about 1 mm, and dynamic viscoelasticity measurement is performed using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200", etc.) under the conditions of shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz, and the glass transition temperature is measured by reading the temperature at which the loss tangent becomes maximum.
[0114] The adhesive layer is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm 2 The glass transition temperature (Tg) after irradiation with light of wavelength 405 nm for 300 seconds (hereinafter, sometimes simply referred to as "glass transition temperature of the adhesive layer after irradiation with light of wavelength 405 nm") is preferably 0°C at the lower limit and 100°C at the upper limit. When the adhesive layer has a glass transition temperature of 0°C or higher after irradiation with light of wavelength 405 nm, the heat resistance of the obtained adhesive laminate film is further improved. When the adhesive layer has a glass transition temperature of 100°C or lower after irradiation with light of wavelength 405 nm, the anchoring force of the adhesive layer to the base layer is further improved, and the handleability of the obtained adhesive laminate film is further improved. The glass transition temperature of the adhesive layer after irradiation with light of wavelength 405 nm is more preferably 5°C at the lower limit and 95°C at the upper limit, and even more preferably 8°C at the lower limit and 90°C at the upper limit. The glass transition temperature of the adhesive layer after irradiation with light having a wavelength of 405 nm was measured by irradiating a sample adhesive layer obtained by the same method as the above-mentioned method for measuring the glass transition temperature of the adhesive layer with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 This can be obtained by measuring a measurement sample that has been irradiated with light of 1000 nm for 300 seconds.
[0115] Methods for adjusting the glass transition temperature of the adhesive layer and the glass transition temperature of the adhesive layer after irradiation with light having a wavelength of 405 nm include, for example, changing the composition of the adhesive layer (e.g., adding an inorganic filler) and adjusting the degree of crosslinking of the curable resin.
[0116] The adhesive layer was formed by irradiating the adhesive laminated film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The preferred lower limit of the peak probe tack value at 60° C. after irradiation for 200 seconds (hereinafter, simply referred to as “peak probe tack value at 60° C. after curing of the adhesive layer”) is 0.30 N / cm 2 After curing, the adhesive layer had a peak probe tack of 0.30 N / cm at 60°C. 2 By virtue of the above, the adhesive laminate film can be more easily peeled off from an adherend having unevenness by heating during peeling. A more preferable lower limit of the peak value of the probe tack at 60° C. after curing of the adhesive layer is 0.40 N / cm 2 , and a more preferable lower limit is 0.50 N / cm 2 It is. Furthermore, the preferred upper limit of the peak value of the probe tack at 60° C. after the adhesive layer is cured is 5.00 N / cm 2 After curing of the adhesive layer, the peak probe tack value at 60°C is 5.00 N / cm 2 The adhesive laminated film has an appropriate heat resistance by being equal to or less than 4.00 N / cm. The more preferable upper limit of the peak probe tack value at 60° C. after curing of the adhesive layer is 4.00 N / cm 2 , and more preferably the upper limit is 2.00 N / cm 2 It is. In this specification, the term "peak probe tack value" means the maximum load applied to a probe when the probe is brought into contact with an adhesive layer using a probe tack measuring device and then pulled up, and specifically means the peak tack value measured using a probe tack measuring device (such as the "Tacking Tester TAC-2" manufactured by RHESCA) under the following measurement conditions: probe diameter 5 mm, pressing speed 0.5 mm / sec, pressing load 98 gf, contact time 10 seconds, and lifting speed 0.1 mm / s. The specific measurement method is as follows: First, an ultra-high pressure mercury lamp is used, with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The cured adhesive layer is irradiated for 200 seconds so that the cured adhesive layer is cut into a test piece having a size of 25 mm in width and 50 mm in length. The test piece thus prepared is then measured using the above-mentioned probe tack measuring device under the above-mentioned measurement conditions in an environment of 60°C and 50% RH, thereby obtaining the value of the adhesive layer.
[0117] The adhesive layer was formed by irradiating the adhesive laminated film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The preferred upper limit of the peak probe tack value at 23° C. after irradiation for 200 seconds so as to obtain a value of 5.00 N / cm 2 After curing, the adhesive layer had a peak probe tack of 5.00 N / cm at 23°C. 2 The more preferable upper limit of the peak value of the probe tack at 23° C. after curing of the adhesive layer is 3.00 N / cm or less, the heat resistance of the adhesive laminate film of the present invention is further improved. 2 , and more preferably the upper limit is 1.00 N / cm 2 It is. The preferred lower limit of the peak value of the probe tack at 23° C. after the adhesive layer is cured is 0.10 N / cm 2 The peak probe tack value at 23° C. after curing of the adhesive layer is 0.10 N / cm 2 By being equal to or greater than this, the adhesive strength at room temperature is further improved. A more preferable lower limit of the peak value of the probe tack at 23° C. after curing of the adhesive layer is 0.20 N / cm 2 , and a more preferable lower limit is 0.25 N / cm 2 It is. In addition, the method for measuring the peak probe tack value at 23°C after the adhesive layer has hardened can be performed by setting the measurement temperature to 23°C for the peak probe tack value at 60°C after the adhesive layer has hardened as described above.
[0118] Methods for adjusting the peak probe tack value at 60°C after the adhesive layer has hardened and the peak probe tack value at 23°C after the adhesive layer has hardened include, for example, changing the composition in the adhesive layer (for example, incorporating a low molecular weight compound having heat resistance (such as an ultraviolet absorber) in the adhesive layer, changing the surface conditioner, incorporating an inorganic filler, etc.).
[0119] The adhesive layer has a thickness of preferably 10 μm at the lower limit and 200 μm at the upper limit. By having the thickness of the adhesive layer within the above range, the water absorption of the obtained adhesive laminated film can be more easily adjusted within the above range. The adhesive layer has a more preferable lower limit of 15 μm, a more preferable upper limit of 100 μm, a still more preferable lower limit of 20 μm, a still more preferable upper limit of 90 μm, and a still more preferable upper limit of 80 μm.
[0120] The method for producing the adhesive laminated film of the present invention is not particularly limited, and it can be produced by using a conventionally known method. Specifically, for example, the above-mentioned curable resin and additives to be blended as necessary are first mixed using a bead mill, ultrasonic dispersion, homogenizer, high-power disperser, roll mill, etc. to prepare an adhesive solution. Next, the obtained adhesive solution is applied to the release-treated surface of a release PET film and dried at 130°C for 1 hour to produce a laminated film having an adhesive layer, and a total of two laminated films are produced by the same method. Then, the adhesive layers of the laminated film are stacked on both sides of the base layer so as to face each other, and the laminated film is aged for 24 hours under an environment of 23°C and 50% RH, whereby an adhesive laminated film can be produced.
[0121] When the adhesive layers of the laminated film are laminated on both sides of the substrate layer so as to face each other, it is preferable to dry the substrate layer before use. By drying the substrate layer before use, the moisture content of the substrate layer of the resulting adhesive laminated film is reduced, so that the occurrence of foaming in a high-temperature environment can be further suppressed. Therefore, the heat resistance of the resulting adhesive laminated film is further improved, and the resulting adhesive film can further suppress peeling of the adhesive laminated film in a high-temperature environment. The drying conditions include, for example, leaving the substrate stationary for 10 minutes in an environment of 130° C. and 50% RH. In the drying treatment of the base layer described above, the base layer alone may be dried, or the base layer and the adhesive layer may be laminated together and dried.
[0122] The adhesive laminated film of the present invention has a preferred lower limit of 10% for the ultraviolet ray transmittance at a wavelength of 405 nm. When the adhesive laminated film of the present invention has an ultraviolet ray transmittance of 10% or more, it becomes possible to irradiate the adhesive layers on both sides with a sufficient amount of ultraviolet ray, so that the adhesive layers on both sides of the adhesive laminated film can be easily cured. The more preferred lower limit of the ultraviolet ray transmittance is 15%, and the even more preferred lower limit is 20%. The preferred upper limit of the ultraviolet transmittance of the adhesive laminated film of the present invention is 70%. By setting the ultraviolet transmittance to 70% or less, irradiation of the adherend with ultraviolet rays can be suppressed when the adhesive laminated film is irradiated with ultraviolet rays, so that the adhesive laminated film can be cured while suppressing deterioration of the quality of the adherend. The more preferred upper limit of the ultraviolet transmittance is 60%, and the even more preferred upper limit is 50%. In the above-mentioned ultraviolet light transmittance at a wavelength of 405 nm of the adhesive laminate film of the present invention, the adhesive layer of the adhesive laminate film is measured using an uncured adhesive layer that is not subjected to a curing operation.
[0123] The adhesive laminated film of the present invention has a preferred lower limit of the total thickness of 50 μm and a preferred upper limit of 500 μm. When the adhesive laminated film of the present invention has a total thickness of 50 μm or more, the adhesive laminated film can have sufficient pressure-sensitive or heat-sensitive adhesive strength at the beginning. When the adhesive laminated film has a total thickness of 500 μm or less, the adhesive laminated film can exhibit high flexibility and can exhibit high conformability to an adherend having unevenness, and when the adhesive laminated film is used as a temporary fixing material, it can be peeled off more easily at the time of peeling. The adhesive laminated film has a more preferred lower limit of 75 μm, a more preferred lower limit of 100 μm, a more preferred upper limit of 400 μm, a more preferred upper limit of 300 μm, a still more preferred upper limit of 180 μm, and a particularly preferred upper limit of 150 μm.
[0124] The adhesive laminate film of the present invention is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 Thus, the preferred lower limit of the 5% weight loss temperature after 200 seconds of irradiation (hereinafter, sometimes simply referred to as "5% weight loss temperature after curing the adhesive layer of the adhesive laminate film of the present invention") is 390°C. When the 5% weight loss temperature after curing the adhesive layer of the adhesive laminate film of the present invention is 390°C or higher, the adhesive laminate film of the present invention has superior heat resistance. A more preferred lower limit of the 5% weight loss temperature after curing the adhesive layer of the adhesive laminate film of the present invention is 400°C, and an even more preferred lower limit is 420°C. Further, there is no particular upper limit to the 5% weight loss temperature after curing of the adhesive layer of the adhesive laminate film of the present invention, but the practical upper limit is about 600°C. The 5% weight loss temperature after curing of the adhesive layer of the adhesive laminated film of the present invention can be measured by simultaneous differential thermal and thermogravimetric measurement. Specifically, it can be measured by, for example, the following method. That is, the adhesive laminate film is cut into a size of 25 mm wide x 50 mm long to prepare a test piece. The obtained test piece is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer is cured by irradiating for 200 seconds so that the adhesive layer is cured. The test piece with the cured adhesive layer is weighed in an aluminum pan, and the aluminum pan is set in a differential thermal-thermogravimetric simultaneous measuring device. When the temperature is increased from 30°C to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, the temperature at the point when the mass of the adhesive laminated film decreases by 5% compared to the mass before heating can be obtained as the 5% weight loss temperature. As the differential thermal-thermogravimetric simultaneous measuring device, for example, STA7200RV (manufactured by Hitachi High-Tech Science Corporation) can be used. Note that the test piece is not laminated with a release PET film to protect the adhesive layer.
[0125] Methods for adjusting the 5% weight loss temperature after curing of the adhesive layer of the above-mentioned adhesive laminate film to within the above-mentioned range include, for example, changing the composition of the adhesive layer (e.g., by incorporating an inorganic filler) and changing the type of base layer.
[0126] The adhesive laminated film of the present invention has excellent heat resistance and can suppress peeling in a high-temperature environment, and therefore can be suitably used for fixing parts to an adherend exposed to high temperatures, particularly for fixing electronic parts in electronic devices exposed to a high-temperature environment for a long period of time. It can also be suitably used for protection and temporary fixation of adherends that undergo high-temperature processing at or above 300° C. In particular, it can be suitably used for protecting electronic components such as semiconductors by temporarily fixing the electronic components to a support plate via the adhesive laminate film or by attaching the adhesive laminate film to the electronic components in order to facilitate handling of the electronic components and prevent damage during processing of the electronic components. The high-temperature processing includes, for example, heat resistance treatment of semiconductors.
[0127] An adhesive laminated film having a base layer and at least one adhesive layer on both sides of the base layer, The present invention also provides a method for producing an adhesive laminate film having a 10% weight loss temperature of 425° C. or higher, the method including a step of drying the base layer. The method for producing an adhesive laminate film of the present invention can produce an adhesive laminate film that has excellent heat resistance and is capable of suppressing peeling in a high-temperature environment.
[0128] The method for producing an adhesive laminated film of the present invention includes a step of drying the substrate layer. By including a step of drying the substrate layer in the method for producing an adhesive laminated film of the present invention, the moisture content in the substrate layer of the obtained adhesive laminated film is reduced, so that the generation of foaming in a high-temperature environment can be further suppressed. As a result, the obtained adhesive laminated film has excellent heat resistance and can suppress peeling in a high-temperature environment. The step of drying the substrate layer can be exemplified by a method of drying the substrate layer in a drying oven, etc. In the step of drying the substrate layer, only the substrate layer may be placed in the drying oven, or the substrate layer and the adhesive layer may be simultaneously dried by placing the substrate layer and the adhesive layer in a laminated state in the drying oven in order to dry the adhesive layer applied to the substrate layer during the production of the adhesive laminated film.
[0129] The method for producing the adhesive laminated film of the present invention preferably includes a step of directly applying an adhesive to the substrate layer. By including a step of directly applying an adhesive to the substrate layer in the method for producing the adhesive laminated film of the present invention, the adhesion between the adhesive layer of the obtained adhesive laminated film and the substrate is further improved, so that the obtained adhesive laminated film has better handling properties.
[0130] In the method for producing the adhesive laminated film of the present invention, it is preferable to subject the substrate layer to a surface treatment before use. By subjecting the substrate layer to a surface treatment, the adhesion between the adhesive layer of the obtained adhesive laminated film and the substrate is further improved, so that the obtained adhesive laminated film has better handling properties. Examples of the surface treatment in the method for producing the adhesive laminated film of the present invention include corona treatment, plasma treatment, sandblasting, chemical etching, and application of a treatment agent (e.g., polyethyleneimine graft polymer, acrylic polymer, polyimide, bismaleimide resin, silane coupling agent, titanium coupling agent, other known adhesion imparting agent, pressure sensitive adhesive, etc.), among which corona treatment is preferred from the viewpoint of easy surface treatment. Examples of the method for corona treatment include corona treatment of the base layer using a high frequency power supply device (manufactured by Kasuga Electric Co., Ltd., "AGI-020", etc.) under conditions of output of 0.3 kW, electrode distance of 1 mm, and speed of 2 m / min. Alternatively, a commercially available product having a base layer subjected to a corona treatment may be used.
[0131] The adhesive laminated film obtained by the method for producing the adhesive laminated film of the present invention has excellent heat resistance and is capable of suppressing peeling in a high-temperature environment, and therefore can be suitably used for fixing parts to an adherend exposed to high temperatures, particularly for fixing electronic parts in electronic devices exposed to a high-temperature environment for a long period of time. The obtained adhesive laminate film can be suitably used for protection and temporary fixation of an adherend that is to be subjected to high-temperature processing at 300° C. or more. For example, during processing of electronic components such as semiconductors, the adhesive laminate film can be suitably used for temporarily fixing the electronic components to a support plate via the adhesive laminate film, or for protecting the electronic components by attaching the adhesive laminate film to the electronic components, in order to facilitate handling of the electronic components and prevent them from being damaged. In particular, the adhesive laminate film can be suitably used for temporary fixation of electronic components.
[0132] Examples of adhesive laminate films that can be produced by the method for producing an adhesive laminate film of the present invention include the adhesive laminate film of the present invention described above. Effect of the Invention
[0133] According to the present invention, it is possible to provide an adhesive laminated film having excellent heat resistance and capable of suppressing peeling in a high-temperature environment. Also, according to the present invention, it is possible to provide a method for producing an adhesive laminated film having excellent heat resistance and capable of suppressing peeling in a high-temperature environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0134] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0135] (Synthesis of polyimide compounds 1-A, 2-A, and 3-A) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075") and 39 g (0.0765 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a brown solid resin (polyimide compounds 1-A, 2-A, and 3-A) having a constitutional unit represented by the following formula (6), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained. The weight average molecular weight of the obtained polyimide compound was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 × 150 mm (manufactured by Waters Corporation) as a column, and was found to be 90,000.
[0136] [ka]
[0137] (Synthesis of polyimide compounds 2-C and 3-C) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075") and 23.732 g (0.0765 mol) of 4,4'-oxydiphthalic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a brown solid resin (polyimide compound 2-C, 3-C) having a constitutional unit represented by the following formula (7), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained. The weight average molecular weight of the obtained polyimide compound was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 × 150 mm (manufactured by Waters Corporation) as a column, and was found to be 110,000.
[0138] [ka]
[0139] (Synthesis of polyimide compound 3-D) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075"), 31.2 g (0.0612 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, and 3.335 g (0.0153 mol) of pyromellitic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a resin (polyimide compound 3-D) having structural units represented by the following formulas (8-1) and (8-2), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained as a brown solid. The weight average molecular weight of the obtained polyimide compound 3-D was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 x 150 mm (manufactured by Waters Corporation) as a column, and was found to be 100,000.
[0140] [ka]
[0141] (Synthesis of polyimide compound 3-E) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075"), 11.7 g (0.0230 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, and 11.674 g (0.0536 mol) of pyromellitic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a resin (polyimide compound 3-E) having structural units represented by the following formulas (9-1) and (9-2), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained as a brown solid. The weight average molecular weight of the obtained polyimide compound 3-E was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 x 150 mm (manufactured by Waters Corporation) as a column, and was found to be 98,000.
[0142] [ka]
[0143] (Synthesis of bismaleimide compound 3-F) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 56 g (0.1 mol) of dimer diamine (Croda, Priamine 1075) and 19.6 g (0.2 mol) of maleic anhydride were added, followed by 5 g of methanesulfonic anhydride. The resulting solution was refluxed for 12 hours, cooled to room temperature, and 300 mL of toluene was added to the flask. The solution was allowed to stand for layer separation, and the lower layer, which was an impurity, was removed. The resulting solution was filtered through a glass frit funnel filled with silica gel, and the solvent was removed under vacuum to obtain a bismaleimide compound 3-F represented by the following formula (10) in the form of a brown liquid.
[0144] [ka]
[0145] (Synthesis of acrylic copolymer 2-E) A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared, and 94 parts by mass of 2-ethylhexyl acrylate, 6 parts by mass of hydroxyethyl methacrylate, 0.01 parts by mass of lauryl mercaptan, and 80 parts by mass of ethyl acetate were added to the reactor, and the reactor was heated to start reflux. Subsequently, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added as a polymerization initiator to start polymerization under reflux. Next, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added one hour and two hours after the start of polymerization, and further, 0.05 parts by mass of t-hexylperoxypivalate was added four hours after the start of polymerization to continue the polymerization reaction. Then, 8 hours after the start of polymerization, an ethyl acetate solution containing a functional group-containing acrylic polymer with a solid content of 55% by mass and a weight average molecular weight of 500,000 was obtained. 3.5 parts by mass of 2-isocyanatoethyl methacrylate was added to 100 parts by mass of the resin solid content of the ethyl acetate solution containing the obtained functional group-containing acrylic polymer and reacted to obtain acrylic copolymer 2-E. The weight average molecular weight of the acrylic copolymer 2-E was 550,000. The weight average molecular weight of the obtained acrylic copolymer 2-E was measured by gel permeation chromatography (GPC, device name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 x 150 mm (manufactured by Waters Corporation) as a column.
[0146] (Synthesis of acrylic copolymer 3-G) A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared, and 93 parts by mass of 2-ethylhexyl acrylate, 1 part by mass of acrylic acid, 6 parts by mass of hydroxyethyl methacrylate, 0.01 parts by mass of lauryl mercaptan, and 80 parts by mass of ethyl acetate were added to the reactor, and the reactor was heated to start reflux. Subsequently, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added as a polymerization initiator to start polymerization under reflux. Next, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added one hour and two hours after the start of polymerization, and further 0.05 parts by mass of t-hexylperoxypivalate was added four hours after the start of polymerization to continue the polymerization reaction. Then, 8 hours after the start of polymerization, an ethyl acetate solution containing a functional group-containing (meth)acrylic polymer with a solid content of 55% by mass and a weight average molecular weight of 600,000 was obtained. 3.5 parts by mass of 2-isocyanatoethyl methacrylate was added to 100 parts by mass of the resin solid content of the ethyl acetate solution containing the obtained functional group-containing (meth)acrylic polymer and reacted to obtain an acrylic copolymer (acrylic copolymer 3-G) having a double bond in the side chain and a weight average molecular weight of 800,000. The weight average molecular weight of the obtained acrylic copolymer 3-G was measured by gel permeation chromatography (GPC) using THF as an eluent and HR-MB-M (product name, manufactured by Waters Corporation) as a column.
[0147] (Synthesis of acrylic copolymer 3-H) Regarding the above-mentioned "(Synthesis of Acrylic Copolymer 3-G)", except that a monomer mixture containing 70 parts by mass of ethyl acrylate and 23 parts by mass of methyl methacrylate was used instead of 93 parts by mass of 2-ethylhexyl acrylate, the same method as for the synthesis of Acrylic Copolymer 3-G was used to synthesize Acrylic Copolymer 3-H, and the weight-average molecular weight was measured. The weight-average molecular weight of Acrylic Copolymer 3-H was 500,000.
[0148] (Preparation of adhesive laminated film) (Examples 1-1 to 1-5, Comparative Examples 1-1 to 1-3) Each of the materials listed in Table 1 was added to 150 mL of toluene and mixed to prepare an adhesive solution. The bismaleimide compound 1-B in Table 1 is a bismaleimide compound represented by the above formula (10) (manufactured by Designer Molecules, "BMI-689"). The obtained adhesive solution was applied with a doctor knife onto the release-treated surface of a 50 μm-thick PET film (release PET film) with one side subjected to release treatment so that the dried thickness was as shown in Table 1, and the coating solution was dried by heating at 130 ° C for 10 minutes to obtain a laminated film (a) having an adhesive layer. Also, a laminated film (b) having an adhesive layer of the thickness shown in Table 1 was produced by the same method. For a base layer of the type and thickness shown in Table 1, the laminated film (a) was laminated on one side and the laminated film (b) was laminated on the other side so that the adhesive layer faces the base layer, and the laminated film was cured at 40 ° C for 24 hours to obtain an adhesive laminated film having an adhesive layer on both sides of the base layer. In the evaluation described below, the adhesive layer derived from the laminated film (a) is referred to as adhesive layer 2 to be bonded to glass, and the adhesive layer derived from the laminated film (b) is referred to as adhesive layer 1 to be bonded to a wafer.
[0149] (Examples 1-6 to 1-8) Adhesive laminate films were produced in the same manner as in Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3, except that the substrate layer shown in Table 1 was pretreated by drying it for 10 minutes in an environment of 130°C and 50% RH, and then laminated with the laminate film (a) and the laminate film (b).
[0150] (Measurement of peak probe tack value after adhesive layer curing) (1) Peak probe tack value at 23°C From the adhesive layer 2 side, an ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating the adhesive layer for 200 seconds so that the adhesive layer was cured, and the adhesive layer on the side not irradiated with light was cut into a size of 25 mm wide x 50 mm long to prepare a test piece. The prepared test piece was measured using a probe tack measurement device (manufactured by RHESCA, "Tacking Tester TAC1000") under the measurement conditions of 23°C, 50% RH, probe diameter 5 mm, pressing speed 0.5 mm / sec, pressing load 98 gf, contact time 10 seconds, and lifting speed 0.1 mm / s to measure the peak probe tack value at 23°C. The results are shown in Table 1.
[0151] (2) Peak probe tack value at 60°C The peak probe tack value at 60° C. was measured in the same manner as in the above-mentioned “(1) Peak probe tack value at 23° C.,” except that the measurement temperature was changed from 23° C. to 60° C. The results are shown in Table 1.
[0152] (Measurement of 5% weight loss temperature after curing the adhesive layer of the adhesive laminate film) The obtained adhesive laminate film was cut into a size of 25 mm wide x 50 mm long to prepare a test piece, and the obtained test piece was irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm from the adhesive layer 2 side. 2 The accumulated light intensity is 20,000 mJ / cm 2The adhesive layer was cured by irradiating for 200 seconds so that the adhesive layer was cured. The test piece with the cured adhesive layer was weighed in an aluminum pan, and the aluminum pan was set in a differential thermal-thermogravimetric simultaneous analyzer (Hitachi High-Tech Science Corporation, "STA7200RV"), and the temperature was raised from 30°C to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere. The temperature at which the mass of the adhesive laminated film decreased by 5% compared to the mass before heating was defined as the 5% weight loss temperature. The results are shown in Table 1. Note that no release PET film to protect the adhesive layer was laminated on the test piece.
[0153] (Measurement of 10% weight loss temperature of adhesive laminated film) Each adhesive laminate film obtained was cut into a size of 5 mm wide x 10 mm long to prepare a test piece. The obtained test piece was weighed into an aluminum pan, and the aluminum pan was set in a differential thermal-thermogravimetric simultaneous measurement device (Hitachi High-Tech Science Corporation, "STA7200RV"), and the temperature was raised at a heating rate of 10°C / min in a temperature range from 30°C to 500°C under a nitrogen atmosphere. The temperature at which the mass of the adhesive laminate film decreased by 10% compared to the mass before heating was taken as the 10% weight loss temperature (°C). Note that no release PET film to protect the adhesive layer was laminated on the test piece. The results are shown in Table 1.
[0154] (Measurement of water absorption rate of adhesive laminate film when left for one day under conditions of 23℃ and 50% RH) Each of the obtained adhesive laminated films was cut into a size of 20 mm wide x 50 mm long to prepare a test piece, which was then dried for 1 hour under an environment of 130°C and 50% RH. The mass W 0 Furthermore, the mass W 0 After the measurement, the test piece is left to stand for one day under conditions of 23°C and 50% RH, and the mass W 1 The obtained W 0 , W 1Using the above, the water absorption rate (%) of the adhesive laminate film when left to stand for one day under the conditions of 23°C and 50% RH was calculated according to the following formula (I). Note that no release PET film was laminated on the test piece to protect the adhesive layer. The results are shown in Table 1. Water absorption rate (%)={(W 1 -W 0 ) / W 0}×100 (I) (W 0 W: Mass of the test piece immediately after drying for 1 hour under 130℃ and 50% RH 1 (Weight of test piece after leaving it for 1 day under the conditions of 23℃ and 50% RH)
[0155] (Measurement of ultraviolet transmittance of adhesive laminated film at 405 nm) Each adhesive laminate film obtained was cut into a size of 50 mm wide x 50 mm long to prepare a test specimen. The ultraviolet transmittance (%) of the prepared test specimen at a wavelength of 405 nm was measured using a spectrophotometer (manufactured by JASCO Corporation, "V-670"). Note that no release PET film was laminated on the test specimen to protect the adhesive layer. The results are shown in Table 1.
[0156] (Measurement of tensile storage modulus at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) The obtained adhesive layer 1 was laminated to a thickness of about 1 mm to prepare a laminate consisting of only the adhesive layer, and the laminate was irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 A measurement sample was prepared by irradiating the adhesive layer with light of 405 nm wavelength for 300 seconds. Dynamic viscoelasticity measurements were performed on the prepared measurement sample using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") under the measurement conditions of shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz, to obtain the tensile storage modulus (Pa) at 23°C after irradiation of the adhesive layer with light of 405 nm wavelength. The results are shown in Table 1.
[0157] (Measurement of anchoring strength to the base layer at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) The adhesive laminate film was irradiated with a super-high pressure mercury lamp from the adhesive layer 2 side at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 An adhesive laminated film was prepared by irradiating the light for 300 seconds. One side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") was attached to a SUS plate that had been washed with ethanol and then wiped dry, and then the adhesive layer 2 of the adhesive laminated film that had been irradiated with light as described above was placed on the other side of the double-sided tape, with the adhesive layer 1 to be measured of the adhesive laminated film facing up. Furthermore, a 25 mm wide silicon tape (manufactured by Sliontec Co., Ltd., "6260-01") was pressed against the exposed adhesive layer 1 to be measured of the adhesive laminated film by moving a 2 kg hand roller back and forth once at a speed of 10 mm / min. A 25 mm wide cut was made along the silicon tape in the adhesive layer 1 pressed against the silicon tape, and the test sample was prepared by curing at 23°C and 50% RH for 1 hour. The obtained test sample was subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "Autograph AGS-X") in accordance with JIS Z0237. The adhesive layer 1 pressed onto the silicon tape was peeled off from the base layer to measure the 90° peel strength (N / 25 mm) of the adhesive layer 1 against the base layer. The obtained 90° peel strength was taken as the anchor strength of the adhesive layer against the base layer at 23°C after irradiation with light of 405 nm wavelength. The results are shown in Table 1.
[0158] The abbreviations for the resin materials contained in the base material layers and the types of base material layers shown in Table 1 are as follows. PEEK: Polyetheretherketone PEN: Polyethylene naphthalate PET: Polyethylene terephthalate PEEK-containing base layer: EXPEEK (Kurabo Industries, Ltd.) PEN-containing base layer: Teonex Q83C (Teijin Ltd.) Polyamide-containing base layer: Uniamide EX-25 (manufactured by Unitika Ltd.) Polyimide-containing base layer: Upilex 25U (manufactured by UBE) PET film: LS-PET (manufactured by Toyo Cross Co., Ltd.)
[0159] [Table 1]
[0160] (Examples 2-1 to 2-2, 2-4 to 2-5, Comparative Examples 2-1 to 2-3) (Preparation of adhesive laminated film) Each material shown in Table 2 was added to 150 mL of toluene and mixed to prepare a solution containing an adhesive resin composition. Note that polyimide compound 2-B is a polyimide compound having a maleimide group represented by the following formula (11) (manufactured by Designer Molecules, "BMI-3000GEL"), and bismaleimide compound 2-D is a bismaleimide compound represented by the above formula (10) (manufactured by Designer Molecules, "BMI-689"). The solution containing the prepared adhesive resin composition was applied to the release-treated surface of a 50 μm-thick PET film (release PET film) with one side subjected to release treatment so that the dried thickness was as shown in Table 2, using a doctor knife, and the coating solution was dried by heating at 130 ° C. for 10 minutes to produce a laminated film (a) having an adhesive layer 1. The obtained laminated film (a) was laminated on one side of the base layer shown in Table 3 so as to face the adhesive layer. By the same method, a laminated film (b) having an adhesive layer 2 having the composition and thickness shown in Table 3 was produced, and the laminated film (b) was laminated on the other side of the base layer so as to face the adhesive layer, thereby obtaining an adhesive laminated film having adhesive layers on both sides of the base layer. In addition, for Comparative Examples 2-1 and 2-2 having an adhesive layer containing a crosslinking agent, the laminated film (a) and the laminated film (b) were laminated on the base layer, and then the laminated film was further aged at 40 ° C. for 3 days to obtain an adhesive laminated film having adhesive layers on both sides of the base layer. In the evaluation described below, the adhesive layer 1 was used as the adhesive layer for adhering to a wafer.
[0161] [ka]
[0162] In formula (11), n is the number of repetitions.
[0163] (Measurement of peak probe tack value after adhesive layer curing) From the adhesive layer 2 side, an ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating for 200 seconds so that the adhesive layer was cured. Otherwise, the same procedures as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3 were carried out to measure the peak probe tack value at 23°C after the adhesive layer was cured, and the peak probe tack value at 60°C after the adhesive layer was cured. The results are shown in Table 2.
[0164] (Measurement of 5% weight loss temperature after curing the adhesive layer of the adhesive laminate film) From the adhesive layer 2 side, an ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiation for 200 seconds so that the temperature was 5% weight loss after the adhesive layer of the adhesive laminated film was cured in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 2.
[0165] (Measurement of 10% weight loss temperature of adhesive laminated film) The 10% weight loss temperature of the adhesive laminated film was measured in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 2.
[0166] (Measurement of tensile storage modulus at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) The laminate, in which the adhesive layer 1 is layered to a thickness of 1 mm, is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2The measurement samples were irradiated for 200 seconds so that the tensile storage modulus was measured at 23° C. after irradiating the adhesive layer with light having a wavelength of 405 nm in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 2.
[0167] (Measurement of anchoring strength to the base layer at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) The adhesive laminate film was irradiated from the adhesive layer 2 side with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm 2 An adhesive laminate film was prepared by irradiating the adhesive layer with light having a wavelength of 405 nm for 300 seconds. Otherwise, the same procedures as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3 were followed to measure the anchoring strength of the adhesive layer to the base layer at 23° C. after irradiation with light having a wavelength of 405 nm. The results are shown in Table 2.
[0168] (Measurement of water absorption rate of adhesive laminate film when left for one day under conditions of 23℃ and 50% RH) The water absorption rate of the adhesive laminated film was measured after leaving it for 1 day under conditions of 23° C. and 50% RH in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 2.
[0169] (Example 2-3) In the above-mentioned "(Measurement of peak value of probe tack after curing of adhesive layer)" and "(Measurement of 5% weight loss temperature after curing of adhesive layer of adhesive laminate film)", a high pressure mercury lamp was used with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 Adhesive laminated films were prepared and measured in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3, except that the adhesive layer was cured by heating in an oven at 150° C. for 30 minutes instead of irradiating for 200 seconds so as to obtain a temperature of 100° C. The results are shown in Table 2.
[0170] The abbreviations for the resins contained in the base layer and the types of base layer shown in Table 2 are as follows. PEN: Polyethylene naphthalate PEEK: Polyetheretherketone PI: Polyimide PET: Polyethylene terephthalate PEN-containing base layer: Teonex Q83C (Teijin Ltd.) PEEK-containing base layer: EXPEEK (Kurabo Industries, Ltd.) PI-containing base layer: Upilex 25U (manufactured by UBE) PET-containing base layer: LS-PET (manufactured by Toyo Cloth Co., Ltd.)
[0171] [Table 2]
[0172] (Example 3-1) (Preparation of adhesive laminated film) Each material shown in Table 3 was added to 150 mL of toluene and mixed to prepare a solution containing an adhesive resin composition. The polyimide compound 3-B shown in Table 3 is a polyimide compound having a maleimide group represented by the above formula (11) (manufactured by Designer Molecules, "BMI-3000GEL"). The solution containing the obtained adhesive resin composition was applied with a doctor knife onto the release-treated surface of a 50 μm-thick PET film (release PET film) with one side subjected to release treatment so that the dried thickness was as shown in Table 3, and the coating solution was dried by heating at 130 ° C for 10 minutes to obtain a laminated film having an adhesive layer. In addition, another same laminated film was produced by the same method. The laminated film was laminated on one side and the other side of the substrate layer of the type and thickness shown in Table 3 so that the adhesive layer faces the substrate layer, and the laminated film was cured for 1 hour in an environment of 23 ° C to obtain an adhesive laminated film having an adhesive layer on both sides of the substrate layer.
[0173] (Measurement of shear storage modulus of adhesive layer (uncured state) at 23°C) The obtained adhesive layers were stacked to a thickness of about 1 mm to prepare a measurement sample of only the adhesive layer. The prepared measurement sample was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") under the measurement conditions of shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz, to measure the shear storage modulus (Pa) of the adhesive layer (uncured state) at 23°C. The results are shown in Table 3.
[0174] (Measurement of tensile storage modulus at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) Before setting the obtained measurement sample in the dynamic viscoelasticity measuring device, the adhesive layer was irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm 2 The tensile storage modulus (Pa) at 23°C after irradiation of the adhesive layer with light of a wavelength of 405 nm was obtained by the same method as in "(Measurement of the shear storage modulus of the adhesive layer (uncured state) at 23°C)" described above, except that a measurement sample was used in which light of a wavelength of 405 nm was irradiated for 300 seconds, and that the dynamic viscoelasticity measurement was performed in tension mode instead of shear mode. The results are shown in Table 3.
[0175] (The adhesive layer was attached to glass, and light was irradiated from the adhesive layer side, after which the tensile storage modulus at 23°C of the adhesive layer that was in contact with the glass was measured.) One surface of the measurement sample obtained in the above-mentioned "(Measurement of the shear storage modulus of the adhesive layer (uncured state) at 23°C)" was attached to glass, and the surface of the measurement sample not in contact with the glass was exposed to light with a wavelength of 405 nm and an illuminance of 80 mW / cm 2 The adhesive layer was attached to glass, and the tensile storage modulus (Pa) of the adhesive layer in contact with the glass after being irradiated with light from the adhesive layer side was obtained by the same method as in "(Measurement of the shear storage modulus of the adhesive layer (uncured state) at 23°C)" described above, except that the measurement sample was removed from the glass after being irradiated with light from the adhesive layer side for 300 seconds, and the measurement was performed in tension mode instead of shear mode in the dynamic viscoelasticity measurement. The results are shown in Table 3.
[0176] (Measurement of anchor strength of adhesive layer (uncured state) to substrate layer at 23°C) One side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") was attached to a SUS plate that had been washed with ethanol and then wiped dry, and the adhesive layer of the obtained adhesive laminate film that was not to be measured was placed on the other side of the double-sided tape, with the adhesive layer of the adhesive laminate film to be measured facing up. Furthermore, a 25 mm wide silicon tape (manufactured by Sliontec Co., Ltd., "6260-01") was pressed against the exposed adhesive layer of the adhesive laminate film to be measured by moving a 2 kg hand roller back and forth once at a speed of 10 mm / min. A 25 mm wide cut was made along the silicon tape in the adhesive layer pressed against the silicon tape, and the test sample was prepared by curing at 23°C and 50% RH for 1 hour. The obtained test samples were subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300mm / min using a tensile tester (Shimadzu Corporation, "Autograph AGS-X") in accordance with JIS Z0237. The adhesive layer pressed onto the silicon tape was peeled off from the base layer to measure the 90° peel strength (N / 25mm) of the adhesive layer against the base layer. The obtained 90° peel strength was taken as the anchor strength of the adhesive layer (uncured state) against the base layer at 23°C. The results are shown in Table 3.
[0177] (Measurement of anchoring strength to the base layer at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) Before attaching one side of a commercially available double-sided tape to a SUS plate that had been washed with ethanol and then wiped dry, the adhesive laminate film was irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 The anchoring strength (N / 25 mm) of the adhesive layer to the base layer at 23°C after irradiation with light of a wavelength of 405 nm was measured in the same manner as in the above-mentioned "(Measurement of anchoring strength of adhesive layer (uncured state) to base layer at 23°C)" except that an adhesive laminate film irradiated with light of a wavelength of 405 nm for 300 seconds was used. The results are shown in Table 3.
[0178] (An adhesive laminate film was attached to glass, and light was irradiated from the adhesive laminate film side. Then, the anchor strength of the adhesive layer that was in contact with the glass to the substrate layer was measured at 23°C.) The adhesive laminated film was attached to the glass, and the surface of the adhesive laminated film not in contact with the glass was exposed to a 405 nm wavelength and 80 mW / cm illuminance. 2 The adhesive laminated film of the adhesive layer was attached to glass, and the anchoring strength (N / 25 mm) of the adhesive layer that was in contact with the glass to the substrate layer at 23°C was obtained by the same method as in "(Measurement of anchoring strength of adhesive layer (uncured state) to substrate layer at 23°C)" above, except that the adhesive laminated film was irradiated with light from the adhesive laminated film side for 300 seconds and then the 90° peeling strength of the adhesive layer that was in contact with the glass to the substrate layer was measured. The results are shown in Table 3.
[0179] (Measurement of glass transition temperature of adhesive layer (uncured state)) Measurement samples were prepared using the same method as described above in "(Measurement of shear storage modulus of adhesive layer (uncured state) at 23°C)". The obtained measurement samples were subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") under the following measurement conditions: shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz, to measure the glass transition temperature (°C) of the adhesive layer (uncured state). The results are shown in Table 3.
[0180] (Measurement of glass transition temperature of substrate layer) For the base material layers shown in Table 3, dynamic viscoelasticity measurements were performed using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") under the measurement conditions of tensile mode, heating rate of 10°C / min, measurement temperature of 0°C to 400°C, and frequency of 10 Hz, to measure the glass transition temperature (°C) of the base material layers. The results are shown in Table 3.
[0181] (Measurement of the melting point of the base layer) For the base material layers shown in Table 3, differential scanning calorimetry (DSC) was performed using a differential scanning calorimeter (Hitachi High-Tech Science Corporation, "DSC-7020") under the measurement conditions of a nitrogen atmosphere, a heating rate of 10°C / min, and a measurement temperature of 30°C to 500°C. From the obtained differential scanning calorimetry curve, the temperature showing the endothermic peak was taken as the melting point (°C) of the base material layer. The results are shown in Table 3.
[0182] (Measurement of peak probe tack value after adhesive layer curing) An ultra-high pressure mercury lamp was used from one adhesive layer side (the adhesive layer side not being measured) with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating for 200 seconds so as to obtain a value of 0.01 mm, and the peak probe tack value was measured for the adhesive layer irradiated with light and the other adhesive layer. Except for this, the peak probe tack value was measured at 23° C. after the adhesive layer was cured, and the peak probe tack value was measured at 60° C. after the adhesive layer was cured, in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 3.
[0183] (Measurement of 5% weight loss temperature after curing the adhesive layer of the adhesive laminate film) An ultra-high pressure mercury lamp was used from one adhesive layer side, with a wavelength of 405 nm and an illumination intensity of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating for 200 seconds so as to obtain a value of 1000 nm, and then the measurement was performed. Otherwise, the 5% weight loss temperature after the adhesive layer of the adhesive laminated film was cured was measured in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 3.
[0184] (Measurement of 10% weight loss temperature of adhesive laminated film) The 10% weight loss temperature of the adhesive laminated film was measured in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 3.
[0185] (Measurement of water absorption rate of adhesive laminate film when left for one day under conditions of 23℃ and 50% RH) The water absorption rate of the adhesive laminated film was measured after leaving it for 1 day under conditions of 23° C. and 50% RH in the same manner as in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-3. The results are shown in Table 3.
[0186] (Example 3-2) In the above-mentioned "(Preparation of adhesive laminate film)", an adhesive laminate film was prepared and measured in the same manner as in Example 3-1, except that a base layer having a surface subjected to corona treatment shown in Table 1 was used, using a high-frequency power supply device (manufactured by Kasuga Electric Co., Ltd., "AGI-020") under conditions of output of 0.3 kW, electrode distance of 1 mm, and speed of 2 m / min. The results are shown in Table 3.
[0187] (Examples 3-3 and 3-7) An adhesive solution was prepared in the same manner as in "(Preparation of adhesive laminate film)" described above. The prepared adhesive solution was directly applied to one side of the substrate layer shown in Table 3 so that the dry thickness was 50 μm, and the substrate was dried at 130° C. for 10 minutes to form an adhesive layer, and then the release-treated surface of a release PET film was laminated so as to face the adhesive layer. The same method was also carried out on the other side of the substrate layer, and the substrate was aged at 23° C. for 1 hour to obtain an adhesive laminate film having adhesive layers on both sides of the substrate layer. The measurements were carried out in the same manner as in Example 3-1, except for the method for producing the adhesive laminated film. The results are shown in Table 3.
[0188] (Examples 3-4 to 3-6, 3-8, 3-10 to 3-13, Comparative Examples 3-1 to 3-3) In the above "(Preparation of adhesive laminate film)", adhesive laminate films were prepared and measured in the same manner as in Example 3-1, except that the type of base layer and the composition of the adhesive layer were changed as shown in Tables 3 and 4. The results are shown in Tables 3 and 4.
[0189] (Examples 3 to 9) (Preparation of adhesive laminated film) An adhesive laminated film having an adhesive layer only on one side of the base layer was obtained in the same manner as in Example 3-1, except that a laminated film was laminated only on one side of the base layer.
[0190] (Measurement of anchor strength of adhesive layer (uncured state) to substrate layer at 23°C) One side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") was attached to a SUS plate that had been washed with ethanol and then wiped dry, and the other side of the double-sided tape was placed over the substrate layer side not having an adhesive layer of the adhesive laminated film of Example 9, with the adhesive layer to be measured facing up. Furthermore, a 25 mm wide silicon tape (manufactured by Sliontec Co., Ltd., "6260-01") was pressed against the exposed adhesive layer to be measured of the adhesive laminated film by moving a 2 kg hand roller back and forth once at a speed of 10 mm / min. A 25 mm wide cut was made along the silicon tape in the adhesive layer pressed against the silicon tape, and the test sample was prepared by curing at 23°C and 50% RH for 1 hour. The obtained test samples were subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "Autograph AGS-X") in accordance with JIS Z0237, and the adhesive layer pressed onto the silicon tape was peeled off from the base layer to measure the anchor strength of the adhesive layer (uncured state) to the base layer at 23°C. The results are shown in Table 3.
[0191] The measurements were carried out in the same manner as in Example 3-1, except for "(Preparation of adhesive laminate film)" and "Measurement of anchor strength of adhesive layer (uncured state) to base layer at 23° C." The results are shown in Table 3.
[0192] The abbreviations for the resins contained in the base layer and the types of base layer shown in Tables 3 and 4 are as follows. PEEK: Polyetheretherketone PET: Polyethylene terephthalate PEN: Polyethylene naphthalate LDPE: Low density polyethylene PEEK-containing base layer: EXPEEK (Kurabo Industries, Ltd.) Polyimide-containing base layer: Upilex 25U (manufactured by UBE) Polyamide-containing base layer: Uniamide EX-25 (manufactured by Unitika Ltd.) PET film: Lumirror S-10 (manufactured by Toray Industries, Inc.) PEN-containing base material layer: Teonex Q83C (manufactured by Toyobo Co., Ltd.) LDPE-containing base layer: LLDPE film A-1 (manufactured by Tamapoly)
[0193] [Table 3]
[0194] [Table 4]
[0195] <Evaluation> The adhesive laminated films obtained in the examples and comparative examples were evaluated by the following methods. The results are shown in Tables 5 to 10.
[0196] (1) Heat resistance The obtained adhesive laminate film was cut into a circle with a diameter of 200 mm. Next, one release PET film was peeled off from the cut adhesive laminate film, and the film was attached to a silicon wafer with a diameter of 200 mm and a thickness of 700 μm under vacuum and at 40° C. Next, the other release PET film was peeled off, and a glass sheet with a diameter of 200 mm and a thickness of 600 μm (manufactured by SCHOTT, “Tempax”) was attached to the surface opposite to the surface attached to the silicon wafer under vacuum and at 90° C. using a pressure lamination device (manufactured by Takatori, “GWSM-300M”) to obtain a laminate. The obtained laminate was heated for 30 minutes using a hot plate (manufactured by ASONE, “ND-3HA”) at 300° C. The heated laminate was observed from the glass side using a stereomicroscope, and was evaluated according to the following criteria. ◯: There was no change in appearance of the adhesive layer of the adhesive laminated film, the substrate layer, and the adhesive surface between the glass and the adhesive laminated film. Δ: There was no change in appearance of the adhesive layer of the adhesive laminate film and the adhesive surface between the glass and the adhesive laminate film, but the base layer was melted. ×: The adhesive layer of the adhesive laminated film was melted, or bubbles were generated on the adhesive surface between the glass and the adhesive laminated film. If the evaluation is not "X", the heat resistance is excellent and peeling in a high-temperature environment can be suppressed. The better the evaluation, the better the heat resistance and the more peeling in a high-temperature environment can be suppressed. In addition, for Examples 1-1 to 1-8, Comparative Examples 1-1 to 1-3, Examples 2-1 to 2-5, and Comparative Examples 2-1 to 2-3, the adhesive layer 1 side was attached to a silicon wafer and the adhesive layer 2 side was attached to glass, and the evaluations were performed.
[0197] (2) Ease of use The obtained adhesive laminate film was cut into a size of 30 cm wide x 30 cm long to prepare a test piece, and the PET film protecting the adhesive layer was gently peeled off by hand from one corner of the test piece. The adhesive laminate film was visually observed during and after the peeling of the PET film, and the handleability of the adhesive laminate film was evaluated according to the following criteria. Note that, for Examples 1-1 to 1-8, Comparative Examples 1-1 to 1-3, Examples 2-1 to 2-5, and Comparative Examples 2-1 to 2-3, the PET film on the adhesive layer 1 side was peeled off and the evaluation was performed. ○: The PET film was peeled off without any problems. ×: When the PET film was peeled off, the adhesive layer peeled off from the base layer, or even a part of the adhesive layer peeled off. Even if the evaluation is "x", the adhesive laminate film of the present invention can be used without any problem depending on the application.
[0198] (3) Heat resistance test at 250℃ One release PET film of the obtained adhesive laminate film was peeled off, and the film was attached to a glass (manufactured by SCHOTT, "Tempax") having a diameter of 200 mm and a thickness of 600 μm under vacuum and at a temperature of 40° C., and the adhesive laminate film was cut into the shape of a silicon wafer. Next, the other release PET film of the attached adhesive laminate film was peeled off, and a silicon wafer having a diameter of 200 mm and a thickness of 700 μm was attached to the surface opposite to the surface attached to the glass under vacuum and at 90° C. using a pressure lamination device (manufactured by Takatori, "GWSM-300M") to produce a laminate. A super-high pressure mercury lamp was used to illuminate the glass side of the obtained laminate with a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiation for 200 seconds so as to obtain the above-mentioned result. The prepared laminate was heated at 250°C using a hot plate (MSA Factory, "PH224 / 225"), and the time from when heating of the laminate began to 0 seconds was set as the time until the adhesive laminate film of the laminate peeled off was measured. The heat resistance of the adhesive laminate film at 250°C was evaluated as follows: "O" if the adhesive laminate film of the laminate did not peel off even after 30 minutes, "△" if the time until the adhesive laminate film of the laminate peeled off was 15 minutes or more but less than 30 minutes, and "X" if the time until the adhesive laminate film of the laminate peeled off was less than 15 minutes. In addition, for Examples 1-1 to 1-8, Comparative Examples 1-1 to 1-3, Examples 2-1 to 2-5, and Comparative Examples 2-1 to 2-3, the adhesive layer 1 side was attached to a silicon wafer and the adhesive layer 2 side was attached to glass, and the evaluations were performed.
[0199] (4) Removability from uneven substrates (4-1) Backed Instead of a silicon wafer, a wafer with a test pattern having a PBO film on the surface (Waltz Corporation, "WALTS-TEG FBW100A-0001JY", Cu pillar height: 35 μm, SnAg height on Cu pillar: 15 μm) was used, and an adhesive laminate film was attached to the surface of the wafer with the Cu pillars, but a laminate was produced in the same manner as in "(3) Heat resistance test at 250°C" above. A super-high pressure mercury lamp was used to illuminate the glass side of the obtained laminate with a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 After irradiating for 200 seconds to cure the adhesive layer, the laminate was heated at 250°C for 30 minutes using a hot plate (MSA Factory, "PH224 / 225"). After air cooling, the laminate was irradiated from the glass side with a wavelength of 355 nm and an irradiation energy density of 700 mJ / cm. 2 A pulsed laser with a frequency of 60 kHz was irradiated onto the entire glass surface, and the glass was peeled off from the adhesive laminate film. A polyimide tape (3M, "5413", width 25 mm) was attached to the adhesive laminate film of the laminate after the glass was peeled off, and the adhesive laminate film was cut to the same width as the polyimide tape to prepare a backing sample for evaluating peelability. For the obtained peelability evaluation sample, the adhesive laminate film was heated to 60°C and the peel angle was adjusted to 180° using an angle-adjustable adhesive / coating peel analysis device VPA-2S (manufactured by Kyowa Interface Science Co., Ltd.), and the adhesive laminate film was peeled off from the uneven wafer, and the 180° peel force (N / inch) was measured. The removability of the adhesive laminate film from the uneven substrate was evaluated based on the following criteria: if the obtained 180° peel force was less than 20 N / inch, it was marked as "○", if it was 20 N / inch or more but less than 30 N / inch, it was marked as "△", and if it was 30 N / inch or more, it was marked as "X". Even if the evaluation is "x", it may still be possible to use it without any problems depending on the application. In addition, for Comparative Examples 2-1 to 2-2 and Comparative Examples 3-1 to 3-2, the evaluation in the above-mentioned "(3) Heat resistance test at 250° C." was "×", and therefore this evaluation was not performed. In addition, for Examples 1-1 to 1-8, Comparative Examples 1-1 to 1-3, Examples 2-1 to 2-5, and Comparative Example 2-3, the adhesive layer 1 side was attached to a wafer with a test pattern having a PBO film on its surface, and the adhesive layer 2 side was attached to glass, and the evaluation was performed.
[0200] (4-2) No backing The removability of the adhesive laminate film from the uneven substrate was evaluated in the same manner as in the evaluation of "(1) with backing" described above, except that the adhesive laminate film was not backed with polyimide tape after the glass of the laminate was peeled off. Even if the evaluation is "x", it may still be possible to use it without any problems depending on the application. In addition, for Comparative Examples 2-1 to 2-2 and Comparative Examples 3-1 to 3-2, the evaluation in the above-mentioned "(3) Heat resistance test at 250° C." was "×", and therefore this evaluation was not performed.
[0201] (5) Heat resistance test at 260℃ The separator on one side of the adhesive laminated film obtained in Examples 3-1 to 3-13 and Comparative Examples 3-1 to 3-3 was peeled off, and the film was manually bonded to a quartz glass having a diameter of 8 inches and a thickness of 800 μm. Furthermore, the separator on the other side of the adhesive laminated film bonded to the quartz glass was peeled off, and a silicon bare wafer having a diameter of 8 inches was bonded to the film using a vacuum bonding device (manufactured by Takatori Corporation, "GWSM-300M") under conditions of a vacuum of 100 Pa, a temperature of 80°C, and a pressure of 0.5 MPa x 300 sec to obtain a glass wafer laminate. An ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 80 mW / cm was used on the glass side of the obtained glass wafer laminate. 2 For Example 3-9 having an adhesive layer on only one side, the separator of the adhesive laminated film was peeled off, and the film was bonded to a bare silicon wafer having a diameter of 8 inches under conditions of a vacuum of 100 Pa, a temperature of 40° C., and a pressure of 0.5 MPa for 300 sec using a vacuum bonding device (manufactured by Takatori Corporation, “GWSM-300M”), and then the film was irradiated with light having a wavelength of 405 nm and an illuminance of 80 mW / cm from the substrate layer side. 2A test sample was obtained by irradiating the sample with light of 1000 nm for 300 seconds. A heat resistance test was performed by placing the prepared test sample in an oven heated to 260° C. and leaving it for 30 minutes in an environment of 260° C. After the heat resistance test, the glass wafer laminate was removed from the oven, and the adhesive surfaces on both sides of the adhesive laminate film were visually observed to confirm the ratio of the area where the adhesive laminate film had peeled off to the entire adhesive surface (peeled area), and evaluated according to the following criteria. ◯: Peeled area was about 5% or less. △: The peeled area was more than 5% and less than about 30%. ×: Peeling area was about 30% or more.
[0202] (6) Weight loss rate of adhesive layer at 300°C The adhesive laminated films obtained in Examples 3-1 to 3-13 and Comparative Examples 3-1 to 3-3 were cut to a size of φ4 mm to prepare test pieces. The obtained test pieces were weighed into an aluminum pan, and the aluminum pan was set in a differential thermal-thermogravimetric simultaneous analyzer "STA7200RV (manufactured by Hitachi High-Tech Science Corporation)". The weight of the test piece when heated from 30°C to 300°C at a heating rate of 10°C / min under a nitrogen atmosphere was compared with the weight before heating to measure the weight loss rate (%) of the adhesive layer at 300°C. Note that no release PET film to protect the adhesive layer was laminated on the test piece. The weight loss rate (%) of the resulting adhesive layer at 300° C. was evaluated as “◯” when it was 4% or less, and as “×” when it was more than 4%.
[0203] [Table 5]
[0204] [Table 6]
[0205] [Table 7]
[0206] [Table 8]
[0207] [Table 9]
[0208] [Table 10] [Industrial Applicability]
[0209] According to the present invention, it is possible to provide an adhesive laminated film having excellent heat resistance and capable of suppressing peeling in a high-temperature environment. Also, according to the present invention, it is possible to provide a method for producing an adhesive laminated film having excellent heat resistance and capable of suppressing peeling in a high-temperature environment.
Claims
1. An adhesive laminated film having a base layer and at least one adhesive layer on both sides of the base layer, The adhesive laminate film has a 10% weight loss temperature of 425° C. or higher, and When left for one day under conditions of 23°C and 50% RH, the water absorption rate is 0.60% or less.
1. An adhesive laminate film comprising:
2. 2. The adhesive laminate film according to claim 1, wherein the adhesive layer contains a curable resin, and the curable resin contains a compound having an imide bond.
3. 3. The adhesive laminate film according to claim 1, wherein the adhesive layer contains a polymerization initiator.
4. 4. The adhesive laminate film according to claim 3, wherein the polymerization initiator comprises a photopolymerization initiator.
5. 3. The adhesive laminate film according to claim 1, wherein the adhesive layer has a thickness of 10 μm or more and 200 μm or less.
6. 3. The adhesive laminate film according to claim 1 or 2, wherein the substrate layer contains a resin (A1) having in its main chain skeleton a repeating unit containing at least one type selected from the group consisting of an ether bond, a ketone group, and an ester bond.
7. The adhesive laminate film according to claim 6, wherein the resin (A1) comprises at least one resin selected from the group consisting of polyether ether ketone (PEEK), polyethylene naphthalate (PEN), polyimide and polyamide.
8. 3. The adhesive laminate film according to claim 1, wherein the thickness of the substrate layer is 50 [mu]m or less.
9. 3. The adhesive laminate film according to claim 1, wherein the ratio of the thickness of the base layer to the thickness of the entire adhesive laminate film is 5% or more.
10. 5. The adhesive laminate film according to claim 4, which has an ultraviolet ray transmittance of 10% or more at a wavelength of 405 nm.
11. 3. The adhesive laminate film according to claim 1, wherein the adhesive laminate film has a total thickness of 50 [mu]m or more and 300 [mu]m or less.
12. 3. The adhesive laminate film according to claim 1, which is used for temporarily fixing electronic parts.
13. An adhesive laminated film having a base layer and at least one adhesive layer on both sides of the base layer, The adhesive laminate film has a 10% weight loss temperature of 425° C. or higher. A method for producing an adhesive laminate film, comprising the steps of: Drying the substrate layer. A method for producing an adhesive laminate film comprising the steps of:
Citation Information
Patent Citations
Releasable tacky adhesive polymer
JP1993032946A
Thermally conductive adhesive tape, article and image display device
JP2015021067A
Base material for heat-resistant adhesive tape and heat-resistant adhesive tape composed of the same
JP2015052050A
Double-sided adhesive sheet
JP2015120876A
Cited By
Adhesive film and wound body
WO2026105817A1
Adhesive film and temporary fixing material
WO2026186764A1